Use of Cr-Zr-N alloy coatings for providing high gloss surfaces

The Cr-Zr-N alloy coating with a specific atomic ratio addresses the issues of poor gloss and corrosion resistance by forming a dense, disordered structure, achieving high gloss and improved corrosion resistance on various substrates.

CN119177442APending Publication Date: 2024-12-24VITALINK INDUSTRY (SHENZHEN) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310748546.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing Cr-Zr-N alloy coatings suffer from poor gloss performance and corrosion resistance, particularly on active metal surfaces, due to the formation of columnar crystals with gaps and defects, leading to inadequate density and susceptibility to corrosion.

Method used

A Cr-Zr-N alloy coating with a specific atomic ratio of Cr, Zr, and N, forming a highly disordered and densely packed structure to reduce columnar cracks, enhancing surface flatness and density, thereby improving gloss and corrosion resistance.

Benefits of technology

The coating achieves high gloss values (≥750GU) and excellent corrosion resistance, with protection times exceeding traditional coatings, and is environmentally friendly, suitable for substrates like aluminum alloys and stainless steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177442A_ABST
    Figure CN119177442A_ABST
Patent Text Reader

Abstract

The invention relates to the use of a Cr-Zr-N alloy coating for providing a surface of a coated article or as a forming base surface of an adjacent alloy coating, the Cr-Zr-N alloy coating comprising a Cr-Zr-N alloy material of formula (CrxZryNz) Ma, M being a doping element and a being 0 or a positive number, with the sum of x and y being 100, 15.0 < = x < = 81.6, 13.7 < = y < = 80.3, 4.7 < = z < = 22.0; the glossiness value test result of the Cr-Zr-N alloy coating meets the threshold value under the condition of at least one forming base surface in aluminum alloy, stainless steel and silicon wafers. The Cr-Zr-N alloy coating has the excellent performance of high glossiness and high corrosion resistance, and can be widely applied to the surfaces of base materials such as aluminum alloy and stainless steel or used for providing a forming base plane of the alloy coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy coatings, and further to application of a Cr-Zr-N alloy coating for providing a high-gloss surface. Background Art

[0002] With the development of science and technology and the improvement of the quality of life, people are not only concerned about the practical performance of products in various fields such as automobiles, wearable products, 3C products, sports products, etc., but also gradually put forward higher requirements for the appearance of products, such as the high gloss of the product surface. Among them, the representative "3C products" among these products are collectively referred to as computer, communication and consumer electronic products, also known as "information appliances", such as computers, tablets, mobile phones or digital audio players. Since 3C products are generally not large in size, they are often collectively referred to as "3C small appliances".

[0003] Gloss is an important parameter of the surface performance of an object, which can reflect the ability of the surface of an object to reflect light. In the field of coatings, high gloss means lower surface roughness and is an important parameter for judging the appearance (aesthetics) characteristics of the coating.

[0004] For 3C digital products, surface gloss is one of the important parameters. Research on alloy coatings with high gloss and corrosion resistance is of great significance for the development of alloy products such as aluminum alloy and stainless steel. The comprehensive performance improvement of both high gloss and corrosion resistance is one of the new research directions for 3C digital products and other products. Summary of the invention

[0005] Based on this, the purpose of the present invention includes providing a Cr-Zr-N alloy coating for providing a high-gloss surface. The Cr-Zr-N alloy coating has the superior properties of high gloss and high corrosion resistance, and can be widely used on the surfaces of substrates such as aluminum alloys and stainless steel, or to provide a forming base surface for the alloy coating, which can improve the aesthetics and corrosion resistance of the coated products.

[0006] In a first aspect of the present invention, a Cr-Zr-N alloy coating is provided for providing a high-gloss surface, wherein the Cr-Zr-N alloy coating is used to provide a surface of a coated product or to be used as a forming base surface of an adjacent alloy coating; the Cr-Zr-N alloy coating comprises a Cr-Zr-N alloy material, wherein the chemical formula of the Cr-Zr-N alloy material is (Cr x Zr y N z )M a, wherein M is a doping element, x, y, z and a are each independently an atomic ratio, and a is 0 or a positive number; taking the sum of x, y and z as 100, 15.0≤x≤81.6, 13.7≤y≤80.3, 4.7≤z≤22.0;

[0007] The glossiness value test conditions of the Cr-Zr-N alloy coating meet at least one of the following conditions:

[0008] Under the test condition of measuring at an angle of 20° and taking aluminum alloy as the forming base surface of the Cr-Zr-N alloy coating, the gloss value of the high gloss surface is ≥750GU;

[0009] Under the test condition of measuring at an angle of 20° with stainless steel as the forming base surface of the Cr-Zr-N alloy coating, the gloss value of the high gloss surface is ≥780GU; and

[0010] Under the test condition of measuring at an angle of 20° and taking a silicon wafer as the molding base surface of the Cr—Zr—N alloy coating, the gloss value of the high gloss surface is ≥900 GU.

[0011] In some embodiments, under the test condition of measuring at an angle of 20° with a silicon wafer as the molding base surface of the Cr—Zr—N alloy coating, the gloss value of the high gloss surface is ≥1000 GU.

[0012] In some embodiments, under the test condition of measuring at an angle of 20° with a silicon wafer as the molding base surface of the Cr—Zr—N alloy coating, the gloss value of the high gloss surface is ≥1100 GU.

[0013] In some embodiments, assuming the sum of x, y and z is 100, 29.7≤x≤81.6, 13.7≤y≤50.1, and 4.7≤z≤20.2.

[0014] In some embodiments, using the Lab test method, the brightness value L of the high gloss surface is ≥70.

[0015] In some embodiments, the Cr—Zr—N alloy coating also serves as a corrosion-resistant coating, a hard coating, or a hard corrosion-resistant coating.

[0016] In some embodiments, the Cr-Zr-N alloy coating satisfies the following two characteristics:

[0017] The X-ray diffraction pattern of the Cr-Zr-N alloy coating has a peak in the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak in the range of 30° to 50° satisfies ≥ 2°;

[0018] In the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy coating, the characteristic atomic spacing is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of The half-height width of at least one diffraction peak in the range satisfies ≥

[0019] In some embodiments, a=0 or 0

[0020] In some embodiments, the doping element is a non-metallic element, a metallic element, or a combination thereof;

[0021] The non-metallic elements include one or more of O, C, B, Si and Ar;

[0022] The metal elements include one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al.

[0023] In some embodiments, the thickness of the Cr-Zr-N alloy coating is d min ~6μm, where d min Selected from 10nm to 50nm.

[0024] In some embodiments, the Cr—Zr—N alloy coating is formed on the surface of any of the following substrates: one of an alloy, a single metal, and an inorganic non-metallic material.

[0025] In some embodiments, the Cr—Zr—N alloy coating is formed on a surface of any of the following substrates: one of aluminum alloy, silicon-based material, and stainless steel.

[0026] In a second aspect of the present invention, there is provided an application of a Cr—Zr—N alloy material for providing a high-gloss surface, wherein the Cr—Zr—N alloy material is as defined in the first aspect of the present invention.

[0027] In the application provided by the present invention, the Cr-Zr-N alloy coating comprises a Cr-Zr-N alloy material with a special atomic ratio, the total content of Cr and Zr is much higher than that of N, the Cr-Zr-N alloy coating has a metallic luster and better glossiness, and can be used to provide a high-gloss surface, which can provide a surface of a coated product (that is, directly provide a high-gloss surface), and can also continue to form a new alloy coating on the Cr-Zr-N alloy coating (in this case, the Cr-Zr-N alloy coating is used as a molding base surface of an adjacent alloy coating), which is conducive to a smoother growth of the new alloy coating.

[0028] ​Furthermore, the special atomic ratio of the three elements Cr, Zr and N causes the atoms to form a highly disordered distribution and a sufficiently dense arrangement, thereby forming a Cr-Zr-N alloy coating with high surface flatness and dense structure. While providing high gloss, it can also reduce or avoid the penetrating column cracks in traditional Cr-Zr-N alloy coatings, thereby also providing excellent corrosion resistance.

[0029] Based on the special "highly disordered and fully densely packed" atomic distribution and arrangement of the aforementioned Cr-Zr-N alloy coating and the resulting high structural density, the surface reflection characteristics of the Cr-Zr-N alloy coating can also be improved to provide a higher brightness value. When providing the surface of a coated product, a surface with high gloss, high brightness value and excellent corrosion resistance can be obtained.

[0030] The aforementioned Cr-Zr-N alloy coating has a dense structure and can also give the alloy coating a higher hardness, better resisting scratches and scrapes; further, the Cr-Zr-N alloy coating can provide a high gloss surface and can also be used as a hard corrosion-resistant coating.

[0031] The Cr-Zr-N alloy coating can provide a high gloss finish on a variety of substrates.

[0032] The method for providing the Cr-Zr-N alloy coating of the present application with a high gloss surface can adopt green and environmentally friendly manufacturing technology. The method is simple and easy to operate. It also has the advantages of being quantifiable, efficient and repeatable, and is suitable for industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. It should also be noted that the drawings are all drawn in a simplified form and are only used to conveniently and clearly assist in explaining the present invention. The various sizes of each component shown in the drawings are arbitrarily shown and may be accurate or may not be drawn according to the actual scale. For example, in order to make the illustration clearer, the size of the components is appropriately exaggerated in some places in the drawings. Unless otherwise specified, the components in the figure are not drawn to scale. The present invention does not limit each size of each component.

[0034] In the following description, the same reference numerals denote the same parts.

[0035] Figure 1Schematic diagrams of the structures of the coated products with the Cr-Zr-N alloy coating of the present invention in some embodiments of the present invention; (A) includes a substrate and the Cr-Zr-N alloy coating of the present invention; (B) includes a substrate, a transition film layer and the Cr-Zr-N alloy coating of the present invention; (C) includes a substrate, a transition film layer, the Cr-Zr-N alloy coating of the present invention and a surface film layer; (D) includes a substrate, the Cr-Zr-N alloy coating of the present invention and a surface film layer;

[0036] Figure 2 Schematic diagram of a device for preparing a Cr-Zr-N alloy coating in one embodiment of the present invention;

[0037] Figure 3 The Cr prepared in Example 1 of the present invention 81.6 Zr 13.7 N 4.7 SEM cross-sectional image of the alloy coating;

[0038] Figure 4 The Cr prepared in Example 1 of the present invention 81.6 Zr 13.7 N 4.7 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0039] Figure 5 The Cr prepared in Example 6 of the present invention 29.7 Zr 50.1 N 20.2 SEM cross-sectional image of the alloy coating;

[0040] Figure 6 The Cr prepared in Example 6 of the present invention 29.7 Zr 50.1 N 20.2 XRD diffraction pattern of alloy coating;

[0041] Figure 7 The Cr prepared in Example 10 of the present invention 61.4 Zr 33.2 N 5.4 SEM cross-sectional image of the alloy coating;

[0042] Figure 8 The Cr prepared in Example 10 of the present invention 61.4 Zr 33.2 N 5.4 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0043] Fig. 9The Cr prepared in Example 11 of the present invention 60.9 Zr 26.1 N 13 SEM cross-sectional image of the alloy coating;

[0044] Fig.10 The Cr prepared in Example 11 of the present invention 60.9 Zr 26.1 N 13 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0045] Fig.11 The Cr prepared in Example 12 of the present invention 53.8 Zr 40.0 N 6.2 SEM cross-sectional image of the alloy coating;

[0046] Fig.12 The Cr prepared in Example 12 of the present invention 53.8 Zr 40.0 N 6.2 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0047] Fig.13 The Cr prepared in Example 13 of the present invention 54.8 Zr 35.1 N 10.1 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0048] Fig.14 The Cr prepared in Comparative Example 1 of the present invention 57.5 Zr 5.0 N 37.5 SEM cross-sectional image of the alloy coating;

[0049] Fig.15 The Cr prepared in Comparative Example 3 of the present invention 37.8 Zr 16.2 N 46 SEM cross-sectional image of the alloy coating;

[0050] Fig.16 The Cr prepared in Comparative Example 3 of the present invention 37.8 Zr 16.2 N 46 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating;

[0051] Fig.17 The Cr prepared in Comparative Example 4 of the present invention 39.6 Zr 19.4 N 41 XRD diffraction pattern (A), selected area electron diffraction pattern (SAED) pattern (B) and radial intensity profile corresponding to SEAD pattern (C) of the alloy coating.

[0052] In the XRD diffraction pattern, the horizontal axis is 2θ, the unit is °, and the vertical axis is the X-ray diffraction intensity (intensity), the unit is au; according to the selected area electron diffraction pattern (SAED) of the alloy coating, the corresponding radial intensity profile is obtained, which is expressed in the form of characteristic atomic spacing (d)-diffraction intensity, with d as the horizontal axis, the unit is angstrom The vertical axis is the electron diffraction intensity (intensity), and the unit is au.

[0053] In the XRD diffraction pattern and the radial intensity profile corresponding to the SAED pattern, au has a well-known meaning in the art.

[0054] In some SEM images, when preparing the cross-section samples to be tested, some cross-section delamination occurs when the silicon wafer is brittle, but it does not affect the observation and analysis of the cross-section morphology. The positions of different structural layers in the substrate and the coating on it can be determined according to the thickness of the corresponding structural layer.

[0055] Description of reference numerals: 1 is a vacuum chamber, 2 is a sample stage, 3 is a DC anode, 4 is a chromium target (also referred to as a Cr target, specifically a Cr target with radio frequency-assisted DC cathode power generation), and 5 is a zirconium target (also referred to as a Zr target, specifically a Zr target with radio frequency-assisted DC cathode power generation);

[0056] 100 is a substrate, 200 is a transition film layer (also called a transition layer), 300 is the Cr-Zr-N alloy coating of the present application, and 400 is a surface film layer (also called a surface layer). DETAILED DESCRIPTION

[0057] The present invention will be further described in detail below in conjunction with the accompanying drawings, embodiments and examples. It should be understood that these embodiments and examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. The purpose of providing these embodiments and examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive. It should also be understood that the present invention can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various changes or modifications without violating the connotation of the present invention, and the equivalent forms obtained also fall within the protection scope of the present invention. For example, the features described or described as part of an embodiment can be combined in another embodiment in a suitable manner to produce a new embodiment. In addition, in the description below, a large number of specific details are given in order to provide a more comprehensive understanding of the present invention. It should be understood that the present invention can be implemented without one or more of these details.

[0058] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing implementation modes and embodiments and are not intended to limit the present invention.

[0059] the term

[0060] Unless otherwise specified or incompatible herewith, the terms and phrases used herein shall have the following meanings:

[0061] The terms "and / or", "or / and", and "and / or" used herein include any one of two or more related listed items, and also include any and all combinations of the related listed items, which include any combination of any two related listed items, any more related listed items, or all related listed items. For example, "A and / or B" includes three parallel solutions: A, B, and "a combination of A and B".

[0062] In the present invention, "plurality", "multiple", "multiple times", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0063] In the present invention, unless otherwise specified, "one or more" means any one of the listed items or any combination of the listed items. Similarly, "one or more" and other expressions that mean "one or more" are also understood in the same way unless otherwise specified.

[0064] As used herein, "combination thereof", "any combination thereof", "any combination thereof" etc. include all suitable combinations of any two or more of the listed items.

[0065] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the ability to implement the technical solution of the present invention, solve the technical problem of the present invention, and achieve the expected technical effect of the present invention.

[0066] Herein, "preferred", "better", "more preferred" and "suitable" are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of the present invention. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.

[0067] In the present invention, "further", "further", "particularly", "for example", "such as", "example", "for example", etc. are used for descriptive purposes, indicating that the previous and subsequent different technical solutions are related in terms of the contents covered, but should not be understood as limiting the previous technical solution, nor can they be understood as limiting the scope of protection of the present invention. In the present invention, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.

[0068] In the present invention, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If multiple "optional" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent of each other. In this application, descriptions such as "optionally contain", "optionally include", etc. mean "contain or not contain". "Optional component X" means that component X exists or does not exist.

[0069] In the present invention, in the "first aspect", "second aspect", "third aspect", "fourth aspect", etc., the terms "first", "second", "third", "fourth", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0070] As used herein, the terms "comprising", "including" and "comprising" are synonymous and are inclusive or open-ended and do not exclude additional, unrecited members, elements or method steps.

[0071] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0072] In the present invention, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values ​​in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum value and the maximum value) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers in the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.

[0073] In this article, unless otherwise specified, "about" means within a certain range above or below the number, and the fluctuation range may vary depending on the type and value of the number. For example, fluctuations within the range of ±2%, ±1%, ±0.5%, etc. of the number are allowed. For example, about 2° can be selected from 2°±0.02°, etc.

[0074] The temperature parameters in the present invention, if not specifically limited, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the precision range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0075] In the present invention, the term "room temperature" generally refers to 4°C to 35°C, such as 20°C ± 5°C. In some embodiments of the present invention, "room temperature" refers to 10°C to 30°C. In some embodiments of the present invention, "room temperature" refers to 20°C to 30°C.

[0076] In the present invention, the term "normal temperature" generally refers to 20°C to 35°C, for example, 20°C to 35°C. In some embodiments of the present invention, "normal temperature" refers to 30°C to 35°C. In some embodiments of the present invention, "normal temperature" refers to 30°C.

[0077] In the present invention, when it comes to the unit of the data range, if there is a unit only after the right endpoint, it means that the units of the left endpoint and the right endpoint are the same. For example, 3-5h means that the units of the left endpoint "3" and the right endpoint "5" are both h (hours).

[0078] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as a reference separately. Unless they conflict with the invention purpose and / or technical solution of the present application, the cited documents involved in the present invention are cited with all contents and all purposes. When the present invention involves cited documents, the definitions of relevant technical features, terms, nouns, phrases, etc. in the cited documents are also cited. When the present invention involves cited documents, the examples and preferred embodiments of the cited relevant technical features may also be incorporated into this application as references, but are limited to the ability to implement the present invention. It should be understood that when the content of the citation conflicts with the description in this application, the present application shall prevail or be modified adaptively according to the description of this application.

[0079] The mass or weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the proportional relationship of the mass or weight between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the mass or weight described in the description of the embodiments of the present invention may be units known in the chemical industry such as μg, mg, g, and kg.

[0080] In the present invention, if there are multiple steps involved in the method flow, unless otherwise specified herein, there is no strict order restriction on the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.

[0081] When describing positional relationships, unless otherwise specified, when an element such as a layer, film, or substrate is referred to as being "on" another film layer, it can be directly on the other film layer or there can be an intermediate film layer. Further, when a layer is referred to as being "under" another layer, it can be directly below or there can be one or more intermediate layers. It is also understood that when a layer is referred to as being "between" two layers, it can be the only layer between the two layers, or there can be one or more intermediate layers.

[0082] Where “including,” “having,” and “comprising” are used herein, it is intended to cover a non-exclusive inclusion, and another component may also be added unless explicit limiting terms such as “only,” “consisting of,” etc. are used.

[0083] Unless mentioned to the contrary, terms in the singular may include plural forms and should not be construed as being one in number.

[0084] At present, in the research field of high gloss alloy coatings, high brightness alloys such as Cr, Al, Zr, Cu, Ag, and Au are generally used. Among them, in the design of Cr-Zr-N alloy coatings, the composition is mainly nitrogen-rich, that is, the nitrogen content in the coating is high (usually higher than 40%). The traditional Cr-Zr-N alloy coating has poor gloss performance and poor corrosion resistance, especially on the surface of active metals. It is difficult to prepare high gloss coatings. After a lot of structural analysis, the inventors of this application speculate that the reasons are as follows: the traditional Cr-Zr-N alloy coating film is prone to form columnar crystals during the nucleation and crystallization growth process, and there are defects such as shadows and gaps between the columnar crystals, which ultimately makes the coating surface not smooth and dense enough, resulting in poor gloss performance and poor corrosion resistance of the coating.

[0085] The inventors of the present application have found through extensive research and experimental analysis that the traditional Cr-Zr-N alloy coating is prone to form columnar crystals during the nucleation and crystallization growth process, and usually has a columnar crystal structure (columnar crystals are formed in more than 90% of cases). Moreover, a high content of columnar crystals will promote the formation of a highly ordered structure arranged in a directional manner. In the highly ordered structure, there are a large number of crystal gap defects caused by crystals, which are mainly manifested as penetrating column gaps. There are shadows between the columnar crystals in the corresponding scanning electron microscope (SEM) cross-sectional diagram, and it is speculated that these penetrating column gaps may lead to poor density and corrosion resistance of the alloy coating. On the one hand, the traditional directional ordered structure is prone to cause the coating to be not dense enough; on the other hand, under corrosive conditions, the corrosive medium can quickly penetrate the coating through the penetrating gaps and react with the substrate, resulting in the corrosion resistance of the alloy coating being not ideal.

[0086] In addition, the alloy materials on the market are mainly protected by means of anodic oxidation, magnetron sputtering, etc. For example, aluminum alloy is mainly protected by anodic oxidation, and its working principle is: the aluminum alloy material is placed in a strong acid or strong alkali solution to form oxides and metal and alloy coatings on the surface to form surface protection; because the solution is a strong acid or strong alkali, the hardness of the product formed by this method is relatively low. In addition, a large amount of wastewater, waste liquid and waste gas are generated during the production process, which is not conducive to environmental protection.

[0087] Based on this, in a first aspect of the present invention, a Cr—Zr—N alloy coating is provided for use in providing a high-gloss surface.

[0088] The Cr—Zr—N alloy coating can be used to provide a surface for a coated product or be used as a forming base surface for an adjacent alloy coating.

[0089] In some embodiments, the Cr-Zr-N alloy coating comprises a Cr-Zr-N alloy material, and the chemical formula of the Cr-Zr-N alloy material is (Crx Zr y N z )M a , wherein M is a doping element, x, y, z and a are each independently an atomic ratio, and a is 0 or a positive number; taking the sum of x, y and z as 100, 15.0≤x≤81.6, 13.7≤y≤80.3, 4.7≤z≤22.0;

[0090] Furthermore, the glossiness value test result of the Cr-Zr-N alloy coating meets the threshold value under at least one of the molding base surfaces of aluminum alloy, stainless steel and silicon wafer;

[0091] Furthermore, the glossiness value test conditions of the Cr-Zr-N alloy coating meet at least one of the following conditions:

[0092] Under the test condition of measuring at an angle of 20° and taking aluminum alloy as the forming base surface of the Cr-Zr-N alloy coating, the gloss value of the high gloss surface is ≥750GU;

[0093] Under the test condition of measuring at an angle of 20° with stainless steel as the forming base surface of the Cr-Zr-N alloy coating, the gloss value of the high gloss surface is ≥780GU; and

[0094] Under the test condition of measuring at an angle of 20° and taking a silicon wafer as the molding base surface of the Cr—Zr—N alloy coating, the gloss value of the high gloss surface is ≥900 GU.

[0095] The Cr-Zr-N alloy coating used in the application provided by the present invention can be recorded as "Cr-Zr-N alloy coating of this application", "Cr-Zr-N alloy coating of this application", "Cr-Zr-N alloy coating described in this application", "Cr-Zr-N alloy coating of the present invention", "Cr-Zr-N alloy coating of the present invention", "Cr-Zr-N alloy coating of the present invention", "Cr-Zr-N alloy coating provided by the present invention" or "Cr-Zr-N alloy coating described in the present invention".

[0096] In the present invention, unless otherwise specified, "Cr-Zr-N alloy" and "CrZrN alloy" both refer to alloys containing Cr, Zr and N elements, and other alloying elements may be contained, and the two can be used interchangeably.

[0097] In the present invention, unless otherwise specified, "Cr-Zr-N alloy material" refers to an alloy material containing Cr, Zr and N elements. Among them, in the Cr-Zr-N alloy material involved in the present invention, the three elements Cr, Zr and N have the above-mentioned specific atomic ratio x:y:z. In the present invention, the form of the Cr-Zr-N alloy material is not particularly limited, and can be, but not limited to, an alloy coating form.

[0098] In the present invention, unless otherwise specified, the "atomic ratio" of two or more elements means the atomic number ratio.

[0099] In the present invention, unless otherwise specified, "Cr-Zr-N ternary alloy" and "CrZrN ternary alloy" both refer to an alloy composed of three elements: Cr element, Zr element and N element.

[0100] In the application provided by the present invention, the Cr-Zr-N alloy coating comprises a Cr-Zr-N alloy material with a special atomic ratio, the total content of Cr and Zr is much higher than that of N, the Cr-Zr-N alloy coating has a metallic luster and better glossiness, and can be used to provide a high-gloss surface, which can provide a surface of a coated product (that is, directly provide a high-gloss surface), and can also continue to form a new alloy coating on the Cr-Zr-N alloy coating (in this case, the Cr-Zr-N alloy coating is used as a molding base surface of an adjacent alloy coating), which is conducive to a smoother growth of the new alloy coating.

[0101] "Gloss" is one of the surface characteristics of an object, which depends on the surface's ability to reflect light in a specular manner; so-called specular reflection refers to the reflection phenomenon in which the reflection angle is equal to the incident angle. "Gloss" is a physical quantity that evaluates the ability of a material surface to reflect light under a set of geometric conditions. Gloss can reflect whether the surface is flat. Therefore, the structural characteristics of the surface morphology can be quantitatively characterized by gloss, and gloss can reflect the structural characteristics of the surface morphology. In the present invention, unless otherwise specified, "gloss value" refers to the value of the gloss of a certain surface, and the unit can be GU. The physical meaning of this unit is: the roughness of the coating or the degree of densification of the coating.

[0102] Those skilled in the art know that the glossiness of the coating surface depends largely on the roughness of the coating surface and is strongly correlated with the density of the surface. The surface density of the coating comes from the overall density of the coating structure. The denser the structure of the coating, the lower its surface roughness and the higher its glossiness.

[0103] In the present invention, the "gloss value" is obtained by testing in the following manner unless otherwise specified: the gloss range is 0-2000GU, the measurement accuracy is ±1%, the angle measurement is 20°, and each sample is tested on a flat surface at multiple (e.g., 5) matrix points and the average value is taken. Further, the testing instrument is a gloss meter. Further, a gloss meter model ZGM1120 produced by Zehntner of Switzerland is used. The test temperature can be room temperature, and further can be 25°C.

[0104] Those skilled in the art will understand that the denser the structure of the coating, the lower its surface roughness, the higher its glossiness, and the stronger its corrosion resistance. Among them, the corrosion-resistant coating must have its own inertness and sufficient isolation. "Original inertness" is specifically expressed as the coating material is sufficiently inert and not easy to chemically react with the corrosive medium in the service environment. "Sufficient isolation" is specifically expressed as the coating structure is dense enough to fully isolate the substrate from the use environment, prevent or delay the reaction between the substrate and the corrosive medium therein, thereby achieving the purpose of corrosion resistance.

[0105] In the present invention, the special atomic ratio of the three elements Cr, Zr and N makes the atoms form a highly disordered distribution and a fully dense arrangement, thereby forming a Cr-Zr-N alloy coating with high surface flatness and good structural density. Therefore, while providing high gloss, it can also reduce or avoid the penetrating columnar cracks in the traditional Cr-Zr-N alloy coating and provide excellent corrosion resistance. The traditional Cr-Zr-N alloy coating with a high content of columnar crystals is nanocrystalline and usually has a large number of penetrating pores. In more detail, the Cr-Zr-N alloy coating used in the present invention has a characteristic structure of "highly disordered and fully densely packed" at the atomic level, contains a very small amount of through-holes or no through-holes, and has a dense coating structure. Among them, the three atoms of Cr, Zr, and N with different radii have a special atomic ratio, which is conducive to the atoms condensing into a highly disordered state during deposition, and then densely stacking in a highly disordered state; the dual characteristics of "highly disordered distribution" and "fully densely packed arrangement" of atoms in the coating make the alloy coating easy to grow densely and improve surface flatness, reduce surface roughness, and improve surface gloss. It can also inhibit the formation of a large number of continuous through-holes, thereby forming an effective isolation between the substrate and the corrosive environment, and significantly improving corrosion resistance. In addition, the Cr-Zr-N alloy coating provided by the present invention contains chromium and zirconium elements, which further makes the coating have sufficient self-chemical inertness in a corrosive environment.

[0106] The alloy coating provided by the present invention effectively reduces the common defects of traditional alloy coatings. For example, the through gaps between grains in the columnar crystal structure coating are greatly reduced or disappear, making the alloy coating more conducive to dense growth, obtaining a flat and low-roughness surface, and giving the Cr-Zr-N alloy coating high gloss, excellent corrosion resistance and high hardness characteristics. Taking the corrosion resistance of aluminum alloy substrates as an example, the Cr-Zr-N alloy coating of the present application is formed on the surface of the aluminum alloy substrate, and the protection time in the salt spray corrosion test can be ≥24 hours, that is, it can pass the 24-hour test, and most embodiments can also pass the 48-hour test; the ASTM B117 salt spray test method can be used, and the following examples can also be referred to. Under the same test conditions, the protection time of traditional hard coatings in the salt spray corrosion test is generally difficult to reach 8 hours.

[0107] In the Cr-Zr-N alloy coating used in the present invention, based on the special atomic ratio of Cr, Zr and N, the Cr and Zr elements are controlled to have a high atomic percentage and a very low nitrogen content, which is much lower than the total content of Cr and Zr. In addition, the atomic size mismatch is good, the random mixing degree is high, and the high content of Cr and Zr is easy to form a strong bond energy, which promotes the rapid growth of the Cr-Zr alloy. The addition of a relatively low amount of nitrogen promotes the re-nucleation of the Cr-Zr alloy to form a Cr-Zr-N alloy. The coating has a high density of nucleation, which promotes the flat growth of the coating surface, forming a "highly disordered and fully densely packed" characteristic structure, so that the surface roughness is low, the glossiness is high, the corrosion resistance is good, and it is also beneficial to improve the hardness. Among them, in terms of atomic size, the Cr atomic radius is The atomic radius of Zr is The atomic radius of N is The atomic sizes of Cr and Zr are close, and the atomic size of N is smaller. During the nucleation process, a small amount of small-sized N atoms can penetrate into the pores of large-sized Cr and Zr metal grains to achieve the effect of filling holes, making the atomic arrangement more dense, which can inhibit the growth defects of the columnar crystal structure of the film and make the coating structure more compact. It can be seen that by carefully selecting the ratio between Cr, Zr, and N, the coating can grow towards densification, thereby increasing the density of the coating, and causing the coating surface to grow towards flatness, thereby achieving the purpose of high gloss. The Cr-Zr-N alloy formed by the present invention not only has good gloss, but also has good corrosion resistance. In addition, it is also beneficial to improve hardness.

[0108] In some embodiments, under the test conditions of measuring at an angle of 20° and taking aluminum alloy as the molding base surface of the Cr-Zr-N alloy coating, the gloss value of the high-gloss surface is ≥800GU, and can also be greater than or equal to one of the following gloss values: 850GU, 900GU, 1000GU, 1100GU, 1150GU, etc.

[0109] In some embodiments, under the test condition of measuring at an angle of 20° and taking stainless steel as the forming base surface of the Cr-Zr-N alloy coating, the gloss value of the high-gloss surface is ≥800GU, and may also be greater than or equal to one of the following gloss values: 850GU, 900GU, 1000GU, 1100GU, 1150GU, etc.

[0110] In some embodiments, under the test conditions of measuring at an angle of 20° and taking a silicon wafer as the molding base surface of the Cr-Zr-N alloy coating, the gloss value of the high-gloss surface is ≥950GU, and may also be greater than or equal to one of the following gloss values: 1000GU, 1050GU, 1100GU, 1150GU, 1200GU, 1150GU, 1200GU, 1250GU, 1300GU, etc.

[0111] In some embodiments, under the test condition of measuring at an angle of 20° with a silicon wafer as the molding base surface of the Cr—Zr—N alloy coating, the gloss value of the high gloss surface is ≥1000 GU.

[0112] In some embodiments, under the test condition of measuring at an angle of 20° with a silicon wafer as the molding base surface of the Cr—Zr—N alloy coating, the gloss value of the high gloss surface is ≥1100 GU.

[0113] In some embodiments, with the sum of x, y and z being 100, 29.7≤x≤81.6, 13.7≤y≤50.1, and 4.7≤z≤20.2. The three atomic ratios of Cr, Zr and N can be more accurately controlled within a better range, which is conducive to forming a denser and smoother Cr-Zr-N alloy coating, thereby better improving one or more of the aforementioned surface gloss, corrosion resistance, hardness and coating surface brightness.

[0114] In some embodiments, based on any of the above suitable embodiments, x, y and z decrease in sequence. At this time, in the Cr-Zr-N alloy material, the Cr content is higher, the Zr content is second, and the N content is the least. This special atomic ratio design makes the atomic random mixing degree higher, which can better improve the density of coating nucleation, thereby better improving one or more properties of the above surface gloss, corrosion resistance, hardness and coating surface brightness.

[0115] In some embodiments, using the Lab test method, the brightness value L of the high gloss surface is ≥ 70. Based on the "highly disordered and fully densely packed" structural characteristics, structural density and surface smoothness of the Cr-Zr-N alloy coating at the atomic level, the reflective properties of the coating surface can also be improved to provide a higher brightness value.

[0116] When the Cr-Zr-N alloy coating of the present application is located on the surface of the coated product (at this time, the Cr-Zr-N alloy coating of the present invention is used as the surface layer of the coated product), the highly dense structure of the alloy coating can also be used to obtain better coating reflection characteristics, thereby providing the coated product with a surface with high brightness. The L value of the Cr-Zr-N alloy coating of the present invention can be ≥70, and some can be as high as 81 and present a high-brightness silver-white color, which is much higher than the L value of the traditional alloy coating (the traditional L value is about 55-65). The high-brightness coating has an aesthetic effect and excellent decorative properties. When applied to the surface of a substrate (such as an aluminum alloy), a high-brightness aesthetic effect can be achieved, so that the coating is closer to the base color, and a colorless differentiation characterization can be achieved. This characteristic makes the Cr-Zr-N alloy coating of the present application have an excellent decorative effect, which is particularly suitable for 3C digital products, such as mobile phone components, and can achieve a high-brightness metal effect. It can also be applied to wearable products, automotive products, sports products and other fields.

[0117] The aforementioned coated products can be intermediate products or final products. The final products can be used or sold directly. The intermediate products can be further processed or assembled with other components into new products.

[0118] When testing the chromaticity value of the alloy coating, the sample to be tested uses a base material that is suitable for practical application, and detects the degree of improvement of the compactness and other properties of the base material by the alloy coating. The L value, a value and b value of the sample can be tested by the CM-3700A-U desktop spectrophotometer produced by Konica Japan. The light receiving system selects the F2 light source, and the average value is taken after testing 6 matrix points for each sample. Among them, the L value represents the brightness value, the a value represents the red and green chromaticity values, and the b value represents the yellow and blue chromaticity values. The larger the L value, the higher the brightness, indicating that the coating surface is denser. The mechanism is as follows: the spectrophotometer is incident light on the surface of the sample to be tested, forming a reflection, and a reflectivity curve can be obtained. The amplitude of the curve can reflect the density of the material, which can be specifically characterized by the L value. On the basis of the same material, the higher its density, the larger the L value it displays.

[0119] In this application, unless otherwise specified, the chromaticity value Lab is tested in the following manner: the light receiving system selects the F2 light source, and each sample is tested at multiple (e.g., 6) matrix points and the average value is taken. Further, a spectrophotometer is used for testing. Furthermore, the test instrument is a CM-3700A-U desktop spectrophotometer produced by Konica of Japan. The test temperature can be room temperature, and further can be 25°C.

[0120] In some embodiments, the Cr—Zr—N alloy coating also serves as a corrosion-resistant coating, a hard coating or a hard corrosion-resistant coating.

[0121] The aforementioned Cr-Zr-N alloy coating has a dense structure and can also give the alloy coating a higher hardness, better resisting scratch and scrape damage; further, the Cr-Zr-N alloy coating can provide a high gloss surface and can also be used as a corrosion-resistant coating, a hard coating or a hard corrosion-resistant coating.

[0122] High-hardness coatings have the effects of high hardness, low friction coefficient and wear resistance. When applied to substrates, such as metal substrates and alloy substrates, high hardness can be achieved, so that the coating has extremely strong high hardness and wear resistance. It is particularly suitable for 3C digital products, mechanical processing, mold manufacturing, geological drilling, textile industry, aerospace, tool surfaces and other fields that have high requirements for hardness and are easy to wear. For example, in the field of portable 3C products, such as the shell parts of mobile phones, they often rub against desktops, pockets, etc., which requires the surface of the shell to be protected by a high-hardness coating to increase the service life of the product. For example, in the field of molds and tools, by adding a high-hardness alloy coating, the wear resistance of the mold or tool can be effectively increased, and the durability of the alloy tool can also be extended. For another example, in the field of aerospace, the device shell forms overheating friction with the air during extremely high-speed operation and is very likely to cause wear. By adding a high-hardness alloy coating on the surface of the shell, friction and wear can be reduced, and the service life of the shell can be increased.

[0123] The application fields of the first aspect are compatible with but not limited to the application fields of traditional hard coatings, such as but not limited to 3C digital products, automotive parts or accessories, mechanical processing, mold manufacturing, geological drilling, textile industry, aerospace and other product or technology fields.

[0124] The Cr-Zr-N alloy coating provided by the present application is not clearly divided into the traditional perfect single crystal or fully amorphous state, but focuses on the close packing degree of atomic arrangement. Based on the specific atomic ratio of Cr, Zr and N, the close packing degree is closely related to the disorder of atomic arrangement and the appropriate mismatch of atomic size; the highly dense Cr-Zr-N alloy coating provided by the present invention has both high gloss and excellent corrosion resistance in performance, and structurally satisfies the requirements of having at least one broad peak (furthermore, there may be no sharp peak, that is, all are broad peaks) in the diffraction angle 2θ (°) range of 30° to 50° in the XRD diagram and the radial intensity profile of the selected area electron diffraction pattern is There is at least one broad peak in the range (furthermore, there may be no sharp peaks, that is, all are broad peaks).

[0125] In some embodiments, the Cr-Zr-N alloy coating satisfies the following two characteristics:

[0126] The X-ray diffraction pattern of the Cr-Zr-N alloy coating has a peak in the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak in the range of 30° to 50° satisfies ≥ 2°;

[0127] In the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy coating, the characteristic atomic spacing is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of The half-height width of at least one diffraction peak in the range satisfies ≥

[0128] The means for structural characterization of the Cr-Zr-N alloy coating in the present invention can also be used to characterize the Cr-Zr-N alloy material of the present invention, and the Cr-Zr-N alloy material may not be limited to the coating form, but may be an independent raw material, such as alloy sheet, alloy plate, etc.

[0129] In the present invention, whether the constituent atoms of the alloy coating have a "highly disordered" state is evaluated by XRD technology. Specifically, the XRD diagram of the Cr-Zr-N alloy coating shows wide and gentle ridges, and these "wide and gentle ridges" are called "broad peaks" of the 2θ (°) diffraction peak. The length of the orderly arrangement of atoms can be obtained by using the Scherrer formula from the half-height width of the wide peak. The calculation method is: D = Kλ / (β·cosθ), where D is the length of the orderly arrangement of atoms (representing the grain size in crystalline materials), K is the Scherrer constant, λ is the wavelength of X-rays; β is the half-height width of the diffraction peak (referring to the width value at half the height of the diffraction peak, Full Width at Half Maximum, FWHM), and θ is the diffraction angle. It can be seen that the half-height width FWHM is inversely proportional to the length D of the orderly arrangement of atoms, and the shorter the length D of the orderly arrangement of atoms, the higher the disorder of the atomic distribution. Therefore, the half-width (FWHM) of the diffraction peak within a specific range in the XRD diagram can be used to reflect the degree of disordered distribution of atoms: the wider the half-width (FWHM), the shorter the length of the ordered arrangement of atoms, and the more disordered the overall atomic distribution; the aforementioned wide and gently raised "broad peak" can reflect the highly disordered distribution of atoms in the material as a whole.

[0130] Generally speaking, the higher the atomic order, the stronger the crystallinity, the easier it is to form large-sized grains over a long distance, the narrower the diffraction peak in the XRD diagram, and high crystallinity is often accompanied by sharp peaks. In the alloy coating of the present invention, the three atoms of Cr, Zr, and N can be highly disordered in the Cr-Zr-N alloy coating as a whole, so that it appears as a wide and gentle ridge (broad peak) in the XRD diagram of the Cr-Zr-N alloy coating, which is manifested as "at least one peak in the diffraction angle 2θ (°) range of 30° to 50° is a "broad peak".

[0131] In the present invention, unless otherwise specified, the "broad peak" in the XRD pattern can be defined as a half-height width satisfying ≥2°. The half-height width of the broad peak can further be ≥2.2°, further ≥2.23°, further ≥2.25°, further ≥2.3°, further ≥3°, further ≥3.5°, further ≥3.92°, further ≥4°, further ≥5°. The half-height width of any "broad peak" in the XRD graph can be independently any of the following values, can be greater than or equal to any of the following values, can be greater than or equal to any of the following values ​​and less than or equal to 10°, and can also be selected from the interval consisting of any two of the following values: 2°, 2.23°, 2.25°, 2.5°, 3°, 3.5°, 3.52°, 3.92°, 4°, 4.5°, 5°, 5.5°, 5.56°, 5.66°, 6°, 6.5°, 7°, 7.5°, 8.42°, 8.5°, 8.85°, 9°, 9.11°, 9.25°, 9.33°, 9.5°, etc. As a non-limiting example, it can be selected from any of the following ranges: 2° to 10°, 2° to 9.5°, 2.20° to 9.35°, 2.23° to 9.33°, 5.66° to 9.33°, etc.

[0132] In the present invention, unless otherwise specified, a "sharp peak" in an X-ray diffraction (XRD) pattern refers to a diffraction peak with a half-height width < 2°.

[0133] In more detail, in the Cr-Zr-N alloy coating provided by the present application, the XRD pattern has peaks in the diffraction angle 2θ(°) range of 30° to 50°, and at least one of the diffraction peaks in the XRD spectrum is a broad peak. The special microstructural state in which at least one peak is a "broad peak" can be represented by "having at least one 2θ(°) diffraction peak with a half-width ≥2° in the range of 30° to 50°" or "having at least one 2θ(°) diffraction peak with a half-width ≥2° in the range of 30° to 50°". The following method can be used to determine whether "having at least one 2θ(°) diffraction peak with a half-width ≥2° in the range of 30° to 50°" is satisfied: in the XRD spectrum, if the half-width value of the 2θ(°) diffraction peak is ≥2°, it is judged as a "broad peak"; if the half-width value of the 2θ(°) diffraction peak is <2°, it is judged as a sharp peak. For a certain specified 2θ(°) position, it can be any of the three states of no peak, broad peak or sharp peak. In the X-ray diffraction (XRD) diagram, the broad peak characteristics of the characteristic diffraction peak of the Cr-Zr-N alloy coating provided by the present invention are more obvious.

[0134] In the traditional Cr-Zr-N alloy coating with a high content of columnar crystals, the diffraction peak in the diffraction angle 2θ (°) range of 30° to 50° often appears as a sharp peak with a half-height width < 2°, and no broad peak appears.

[0135] In the present invention, conventional instruments and methods in the art can be used to obtain the XRD pattern of the alloy coating, for example, a German Bruker D8 Advance XRD diffractometer can be used.

[0136] In some embodiments, the X-ray diffraction pattern of the Cr-Zr-N alloy coating of the present invention has a peak in the diffraction angle 2θ(°) range of 30° to 50°, and at least one 2θ(°) diffraction peak in the range of 30° to 50° is a broad peak, and the half-width value of the broad peak can be referred to the examples in the context; taking the half-width of the broad peak ≥2.23° as an example, at least one 2θ(°) diffraction peak in the range of 30° to 50° satisfies ≥2.23°.

[0137] In some embodiments, the X-ray diffraction pattern of the Cr—Zr—N alloy coating of the present invention has a broad peak within a diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of the broad peak can be found in the examples in the context.

[0138] In some embodiments, the X-ray diffraction pattern of the Cr—Zr—N alloy coating of the present invention has two or more broad peaks within a diffraction angle 2θ (°) range of 30° to 50°, and the half-height widths of these broad peaks can be independently referred to the examples in the context.

[0139] In some embodiments, in the X-ray diffraction pattern of the Cr-Zr-N alloy coating of the present invention, all 2θ(°) diffraction peaks within the diffraction angle 2θ(°) range of 30° to 50° are broad peaks, that is, there are no sharp peaks at this time, and the half-height widths of these broad peaks can be independently referred to the examples in the context.

[0140] In some embodiments, the X-ray diffraction pattern of the Cr-Zr-N alloy coating of the present invention has a peak in the diffraction angle 2θ(°) range of 30° to 50°, and the half-height width of the 2θ(°) diffraction peak in the range of 30° to 50° each independently satisfies ≥2°, further can each independently satisfy ≥2.2°, further can each independently satisfy ≥2.23°, further can each independently satisfy ≥2.25°, further can each independently satisfy ≥2.3°, further can each independently satisfy ≥3°, further can each independently satisfy ≥3.5°, further can each independently satisfy ≥4°, further can each independently satisfy ≥5°, further can each independently satisfy ≥5.6°.

[0141] In some embodiments, the X-ray diffraction pattern of the Cr-Zr-N alloy coating of the present invention has only one diffraction peak within the diffraction angle 2θ (°) range of 30° to 50°, and the diffraction peak is a broad peak.

[0142] In some embodiments, the X-ray diffraction pattern of the Cr—Zr—N alloy coating is obtained by Cu target Kα radiation.

[0143] In the present invention, the following instruments and methods can be used to obtain the XRD pattern of the alloy coating: using a German BrukerD8 Advance XRD diffractometer, in θ-2θ mode, using Cu target Kα rays, a wavelength λ of 0.15406nm, the X-ray tube is controlled at 40kV and 40mA, the scanning range is 20° to 80°, and precise scanning measurement is performed with a step size of 0.01°.

[0144] The half-width value can be obtained by conventional analysis methods in the art (including but not limited to analysis software provided by the instrument supplier). For example, the step of obtaining the half-width value may include: firstly performing correction processing on the diffraction peak, which may include: smoothing, subtracting the background, removing the Kα2 line, subtracting the instrument broadening, etc., and fitting the diffraction peak with the Pseudo-Voigt function to obtain the half-width value of the diffraction peak.

[0145] The analysis software is not particularly limited. Without limitation, EDP2XRD software (version 1.0.0, copyright by Hongwei Liu, The Australian Center for Microscopy and Microanalysis, The University of Sydney) can be used to process the spectrum data. For example, the following method can be used: first, a scale calibration is performed, and then the center of the diffraction ring transmission spot is determined, and then converted into an XRD spectrum (wherein the electron wavelength is 0.00251 nanometers and the X-ray wavelength is 0.154 nanometers; the diffraction peak is deducted from the straight line background, and then fitted with a Voigt function to obtain the half-height width of the corresponding diffraction peak.

[0146] Regarding the characterization of the degree of atomic density in alloy coatings, traditional XRD patterns cannot be used to characterize it well. This is because: when detecting physical vapor deposition (PVD) films or coatings at the atomic scale (such as diameter <3nm), the XRD method often has insufficient resolution due to the large wavelength of X-rays (>0.1nm), and is not suitable for PVD films or coatings with low order (such as grains or amorphous grains with a diameter <3nm).

[0147] In the present invention, whether the atoms constituting the coating have reached "sufficiently densely packed" is evaluated by the selected area electron diffraction pattern (Selected Area Electron Diffraction, SAED). The electron wave is selected because its wavelength is significantly smaller (<0.01nm), so the resolution is higher. Specifically, if there are only continuous diffraction rings with consistent brightness on the SEAD graph, and the diffraction rings are relatively wide, it indicates that the atoms in the coating are densely packed in a highly random mixed manner. In order to quantitatively characterize, the SAED spectrum can be converted into a characteristic atomic spacing (d)-radial intensity profile, wherein the characteristic atomic spacing (d) is the horizontal coordinate and the diffraction intensity is the vertical coordinate. If the diffraction rings in the SEAD are relatively wide, then correspondingly, the half-height width of the radial intensity profile is relatively wide, reflecting that the atomic arrangement in the alloy coating is densely packed.

[0148] In this application, in terms of atomic size, the Cr atomic radius is The atomic radius of Zr is The atomic radius of N is The three atoms with different diameters have a suitable atomic size mismatch, and under the condition of high random mixing, a fully dense structure can be formed. In the growth process of PVD film or alloy coating, the fully dense stacking of atoms in Cr-Zr-N alloy coating makes the alloy coating easy to grow densely, which can inhibit the formation and growth of columnar crystals originally caused by local ordering, and then make it difficult for continuous through-type pores to form in large quantities. Thus, the half-height width of the radial intensity profile can be used as the characteristic parameter of the fully dense structure of the alloy coating to reflect the dense packing of atoms in the alloy coating. The larger the value of the half-height width, the better the dense packing of atoms in the alloy coating. In short, the present invention adopts the half-height width of the radial intensity profile of SAED as the characteristic parameter of fully dense atomic stacking, which is in line with scientific principles and has scientificity.

[0149] When the half-height width of the radial intensity profile is greater than a certain threshold, the atoms in the coating can be fully densely packed. According to a large number of experimental explorations by the inventors, in the present invention, unless otherwise specified, the half-height width threshold for judging whether the atoms are fully densely packed in the SAED-radial intensity profile is determined as That is, the half-height width ≥ When the atoms are fully packed together,

[0150] In the present invention, a transmission electron microscope (TEM) technique may be used to obtain a radial intensity profile of a characteristic atomic spacing (d) of an alloy coating sample.

[0151] In the present invention, the radial intensity profile corresponding to the selected area electron diffraction pattern of the alloy coating can be recorded as a SAED-radial intensity profile, and can also be recorded as a characteristic atomic spacing-intensity quantitative spectrum of the selected area electron diffraction pattern (SAED pattern). The selected area electron diffraction pattern obtained by transmission electron microscopy can be recorded as a TEM selected area electron diffraction pattern, and can also be recorded as a TEM-SAED pattern. The SAED-radial intensity profile obtained by transmission electron microscopy can also be recorded as a TEM-SAED-radial intensity profile.

[0152] In the present invention, the alloy coating (including the Cr-Zr-N alloy coating of the present invention) can be obtained by using conventional instruments and methods in the art, and the corresponding radial intensity profile can be obtained according to the selected area electron diffraction pattern (SAED) of the alloy coating. It is expressed in the form of characteristic atomic spacing (d)-diffraction intensity, with d as the horizontal coordinate and the unit being angstroms. The vertical axis represents the electron diffraction intensity.

[0153] In the present invention, unless otherwise specified, in the radial intensity profile of the SAED pattern, the half-height width of the diffraction peak is ≥ It is judged as a broad peak; the half-height width of the diffraction peak is < For a specific characteristic atomic spacing, it can be any of the three states of no peak, sharp peak or broad peak. In the radial intensity profile, the broad peak characteristics of the characteristic diffraction peak of the Cr-Zr-N alloy coating provided by the present invention are more obvious. Unless otherwise specified, the "broad peak" in the radial intensity profile of the selected area electron diffraction pattern (SAED pattern) refers to a half-height width ≥ The diffraction peak of "peak" refers to the half-height width < diffraction peaks.

[0154] In the present invention, the radial intensity profile or SAED-radial intensity profile, unless otherwise specified, can be obtained using TEM technology.

[0155] In the present invention, unless otherwise specified, the "broad peak" in the radial intensity profile corresponding to the SAED pattern can be defined as the half-height width satisfying ≥ The half-height width of the broad peak can be further ≥ Further, you can ≥ Further, you can ≥ Further, you can ≥ Further, you can ≥

[0156] In the present invention, the following transmission electron microscopy (TEM) method can be used (but not limited to) to obtain the half-width at half maximum data in the radial intensity profile corresponding to the selected area electron diffraction pattern:

[0157] TEM test sample preparation: The Helios 5CX model focused ion beam (FIB) of Thermo Fisher Co., Ltd. of the United States was used to thin the sample to obtain an electron transparent, TEM-observable planar sample.

[0158] SAED image acquisition: A Talos F200x transmission electron microscope (TEM) of Thermo Fisher Co., Ltd. of the United States was used with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm to obtain the selected area electron diffraction pattern (SAED) of the sample. Based on the selected area electron diffraction pattern (SAED) image, a radial intensity profile was obtained, and the half-height width value of the diffraction peak was obtained by using the integrated half-height width assignment.

[0159] According to the principle that the half-width of the diffraction peak in the radial intensity profile corresponds to the width of the diffraction ring in the selected area electron diffraction pattern (SAED) pattern, the selected area electron diffraction pattern (SAED) pattern of the alloy coating can be converted into the corresponding radial intensity profile.

[0160] Those skilled in the art know that the larger the width of the diffraction ring in the selected area electron diffraction pattern, the stronger the random mixing degree of the atoms, and the more densely packed the atoms are in the Cr-Zr-N alloy coating of the present invention; the half-width of the diffraction peak in the radial intensity profile is a quantitative indicator of the width of the diffraction ring, and the larger the half-width value, the more densely packed the atoms are.

[0161] In some embodiments, the selected area electron diffraction pattern (SAED) of the Cr-Zr-N alloy coating of the present invention is obtained using a transmission electron microscope (TEM) characterization technique, with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm.

[0162] In some embodiments, in the radial intensity profile of the selected area electron diffraction pattern of the Cr-Zr-N alloy coating of the present invention, has at least one half-width ≥ diffraction peaks.

[0163] In the radial strength cross-sectional diagram of the Cr-Zr-N alloy coating provided by the present invention, The half-height width of the diffraction peak in the range has an upper limit due to the atomic close packing limit. Non-limiting examples of the upper limit are as follows:

[0164] In the present invention, the half-height width of the "broad peak" in the radial intensity profile corresponding to the SAED pattern can be independently any of the following values, can be greater than or equal to any of the following values, can be greater than or equal to any of the following values ​​and less than or equal to the aforementioned upper limit value (such as ), and can also be independently selected from an interval consisting of any two of the following values: As a non-limiting example, the half-height width of the "broad peak" in the radial intensity profile corresponding to the SAED pattern can be selected from any of the following ranges: etc.

[0165] In some embodiments, in the radial strength profile of the Cr-Zr-N alloy coating, The half-height width of the diffraction peak in the range ≤

[0166] In some embodiments, in the radial strength profile of the Cr-Zr-N alloy coating of the present invention, The half-height width of the diffraction peak within the range can be independently any of the following values, can be independently greater than or equal to any of the following values, and can also be independently selected from an interval consisting of any two of the following values: As a non-limiting example, any of the following ranges may be selected: wait.

[0167] In some embodiments, the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy coating of the present invention is There is one broad peak in the range, and its half-height width can be found in the examples in the context.

[0168] In some embodiments, the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy coating of the present invention is There are 2 or more broad peaks in the range, and their half-height widths can be independently determined by referring to the examples in the context.

[0169] In some embodiments, the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy coating of the present invention is All diffraction peaks within the range are broad peaks, and the half-height width of all diffraction peaks meets ≥ See also context definition.

[0170] In some embodiments, the characteristic atomic spacing of the Cr-Zr-N alloy coating of the present invention is obtained using TEM diffraction data; wherein, the TEM diffraction test of the alloy coating is performed using an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm.

[0171] In some embodiments, the TEM test uses a mode with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm to obtain a selected area electron diffraction pattern (SAED) of the Cr—Zr—N alloy coating.

[0172] Regarding the intrinsic mechanism analysis of the excellent corrosion resistance of the Cr-Zr-N alloy coating provided by the present application, the inventors of the present application have found through a large number of experimental explorations that for the Cr-Zr-N alloy coating, when the following two conditions are met at the same time: (1) the diffraction angle 2θ (°) in the XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, and (2) the radial intensity profile of the selected area electron diffraction pattern is The prepared Cr-Zr-N alloy coating has excellent corrosion resistance if only the XRD diffraction pattern has at least one broad peak in the range of 30° to 50° in the diffraction angle 2θ (°) and the radial intensity profile of the SAED pattern has at least one broad peak in the range of 30° to 50°. If there is no broad peak in the range, the prepared Cr-Zr-N alloy coating may have poor corrosion resistance. For example, the corresponding aluminum alloy substrate sample may not pass the 24h or 48h salt spray corrosion test. The XRD diffraction pattern has at least one broad peak in the range of 30° to 50°, while the diffraction angle 2θ(°) in the XRD diffraction pattern has no broad peak in the range of 30° to 50°, which may also lead to the poor corrosion resistance of the Cr-Zr-N alloy coating.

[0173] In some embodiments, based on any of the above suitable embodiments, the thickness of the Cr-Zr-N alloy coating is d min ~6μm, where d min It can be selected from 10nm to 50nm, d min It can also be any of the following thicknesses, or a range selected from any two of the following thicknesses: 10nm, 20nm, 25nm, 30nm, 40nm, 50nm, etc.; for example, the thickness of the Cr-Zr-N alloy coating can be 25nm~6μm, 30nm~6μm, 40nm~6μm, 50nm~6μm, 1.0μm~2.5μm, 1.0μm~2.0μm, etc.

[0174] By controlling the Cr-Zr-N alloy coating of the present invention to have a more appropriate thickness, the high hardness characteristics and / or corrosion resistance of the alloy protective coating can be better utilized. The thicker the Cr-Zr-N alloy coating, the more conducive it is to improving the hardness and / or corrosion resistance of the alloy coating. The Cr-Zr-N alloy coating provided by the present invention can have both high hardness characteristics and high corrosion resistance at a relatively low thickness, thereby saving raw materials, simplifying the process, shortening the production cycle, and significantly reducing costs.

[0175] In some embodiments, the Cr—Zr—N alloy coating has a thickness of 10 nm to 6 μm.

[0176] In some embodiments, the Cr—Zr—N alloy coating has a thickness of 25 nm to 6 μm.

[0177] In some embodiments, the Cr—Zr—N alloy coating has a thickness of 1 μm to 2.5 μm.

[0178] In addition, when the thickness of the alloy coating is relatively thin, the formed coated product can also present a silvery white metallic color, which is close to the metallic color of the substrate, which is conducive to achieving a beautiful decorative effect without changing the color of the substrate.

[0179] The Cr-Zr-N alloy coating provided in each embodiment of the present invention may be doped with other elements or may not be doped with other elements, and can be flexibly selected according to the additional functional requirements of the alloy material and / or the alloy coating. It can be understood that in the present invention, when doping elements are contained, the type and amount of doping elements are limited to not affecting the high gloss and corrosion resistance of the Cr-Zr-N alloy coating.

[0180] In the present invention, the chemical formula of the Cr-Zr-N alloy material contained in the Cr-Zr-N alloy coating can be expressed as (Cr x Zr y N z )M a , wherein x, y and z are each independently an atomic ratio and a positive number, M is a doping element, and a is an atomic ratio of the M element and is 0 or a positive number. When a is 0, the Cr-Zr-N alloy material does not contain a doping element, corresponding to a Cr-Zr-N ternary alloy material. When a>0, the Cr-Zr-N alloy material contains a doping element, wherein a / (x+y+z) is numerically equal to the relative atomic percentage of the doping element relative to Cr, Zr and N, and a / (x+y+z+a) is numerically equal to the atomic percentage of the doping element in the Cr-Zr-N alloy material.

[0181] Unless otherwise specified, the Cr-Zr-N alloy material involved in each embodiment of the present invention mainly contains three elements: Cr, Zr and N. Furthermore, the sum of the atomic ratios of the three elements accounts for ≥95% of the sum of the atomic ratios of all elements in the Cr-Zr-N alloy material (corresponding to 0≤a / (x+y+z+a)≤0.05, such as 0≤a / (x+y+z)≤0.05), further such as ≥98% (corresponding to 0≤a / (x+y+z+a)≤0.02, such as 0≤a / (x+y+z)≤0.02), and further such as Cr-Zr-N ternary alloy material (at this time, a=0). By limiting the content of doping elements, the influence of doping elements on the highly disordered and fully densely packed atoms in the Cr-Zr-N alloy coating of the present application can be minimized, which is beneficial to reduce the elements required for doping or reduce the difficulty of doping, simplify the preparation process, and promote the coordinated deposition of Cr, Zr and N to form a denser coating, thereby better improving one or more of the aforementioned surface gloss, corrosion resistance, hardness and coating surface brightness.

[0182] In some embodiments, a / (x+y+z)=0. At this time, corresponding to the Cr-Zr-N ternary alloy material, the composition is simple, and it is easier to prepare and control. The Cr-Zr-N ternary alloy coating formed at this time can obtain a dense structure.

[0183] In some embodiments, 0≤a / (x+y+z+a)≤0.05. In some embodiments, a=0 or 0

[0184] In some embodiments, 0

[0185] In some embodiments, 0

[0186] ​​​In some preferred embodiments, 0

[0187] In some embodiments, the doping element is a non-metallic element, a metallic element or a combination thereof, which can be flexibly selected according to the additional functional requirements of the Cr-Zr-N alloy coating. It is understood that in the present invention, when the doping element is contained, the type and doping amount of the doping element are limited to being able to form the Cr-Zr-N alloy coating structure of the present invention without affecting the excellent high gloss and corrosion resistance.

[0188] Without limitation, the non-metallic element may include one or more of O, C, B, Si and Ar. Without limitation, the metal element may include one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al.

[0189] In some embodiments, 0≤a / (x+y+z+a)≤0.05 (can also be selected from any suitable range or any suitable value mentioned above), and the doping element may include one or more metal elements of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al.

[0190] ​It should be noted that in any embodiment of the present application, the Cr-Zr-N alloy coating provided by the present application and the Cr-Zr-N alloy material involved allow the presence of inevitable impurities introduced during the preparation process. "Inevitable impurities" are not intentionally added impurities, and the main reason for their existence is that they are unintentionally introduced during the preparation process; non-limiting examples of "inevitable impurities" include, for example, elements such as C and O present in the air, and may also come from components in raw materials or equipment. The atomic content of "inevitable impurities" in the Cr-Zr-N alloy coating is usually trace or micro, which can generally be ignored, such as less than 0.01% atomic content. Taking the technical solution of "Cr-Zr-N alloy coating is a Cr-Zr-N ternary alloy material composed of Cr, Zr and N elements" as an example, at this time, theoretically, the Cr-Zr-N alloy coating is composed of three elements: Cr, Zr and N, but trace or micro amounts of other elements other than Cr, Zr and N may be introduced during the preparation process, such as C, O, etc.

[0191] The Cr-Zr-N alloy coating can provide a high gloss finish on a variety of substrates.

[0192] In some embodiments, the substrate may be, but is not limited to, one of an alloy, a single-substance metal, and an inorganic non-metallic material. Without limitation, the material type of the alloy may include one or more of a nickel-based, iron-based, tungsten-based, titanium-based, silicon-based, aluminum-based, copper-based, cobalt-based, zirconium-based, and zinc-based. Without limitation, the single-substance metal may be any one of zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver, and chromium. Without limitation, the inorganic non-metallic material may include one or more of ceramics and glass. Without limitation, the inorganic non-metallic material may include a silicon wafer.

[0193] In some embodiments, the substrate is one of aluminum alloy, silicon-based material and stainless steel. The silicon-based material may be a silicon wafer or a silicon-containing compound, and further, the silicon-containing compound may include but is not limited to one or more of silicon oxide, silicon-carbon compound, and silicon-nitrogen compound. The stainless steel alloy may be but is not limited to any one of austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, etc.

[0194] The Cr-Zr-N alloy coating of the present application may exist in a coated product and provide a high-gloss surface. It can provide the surface of the coated product (that is, directly provide a high-gloss surface), and can also continue to form a new alloy coating on the Cr-Zr-N alloy coating (in this case, the Cr-Zr-N alloy coating is used as a molding base surface for the adjacent alloy coating), which is conducive to a smoother growth of the new alloy coating.

[0195] In some embodiments, the coated product includes a substrate and the Cr-Zr-N alloy coating described in the first aspect of the present invention (ie, the Cr-Zr-N alloy coating of the present application); wherein the Cr-Zr-N alloy coating is located on at least one side of the substrate.

[0196] The Cr-Zr-N alloy coating provided by the present invention can be located on one side or both sides of the substrate.

[0197] In some embodiments, the surface material of the substrate is one of an alloy, a single metal and an inorganic non-metallic material. Without limitation, the material type of the alloy may include one or more of a nickel-based, iron-based, tungsten-based, titanium-based, silicon-based, aluminum-based, copper-based, cobalt-based, zirconium-based and zinc-based. Without limitation, the single metal may be any one of zinc, gold, platinum, zirconium, hafnium, niobium, tantalum, nickel, copper, aluminum, iron, silver and chromium. Without limitation, the inorganic non-metallic material may include one or more of ceramics and glass. Without limitation, the inorganic non-metallic material may include a silicon wafer.

[0198] Furthermore, the Cr-Zr-N alloy coating provided by the present invention can be applied to a variety of substrates, the materials of the substrates include but are not limited to alloys, elemental metals and other materials, and can also be used for other types of substrates such as inorganic non-metallic materials (such as silicon wafers, ceramics, glass).

[0199] In some embodiments, the surface material of the substrate is one of light alloys or one of stainless steel alloys; optionally, the light alloy may include one or more of titanium alloy, aluminum alloy and magnesium alloy.

[0200] In some embodiments, the surface material of the substrate is one of light alloys; further, the light alloy may include one or more of titanium alloy, aluminum alloy and magnesium alloy.

[0201] In some embodiments, the surface material of the substrate is one of stainless steel alloys. Further, the stainless steel alloy can be any one of austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, etc.

[0202] In some embodiments, the coated article satisfies one or more of the following features:

[0203] The Cr-Zr-N alloy coating is in direct contact with the substrate (in this case, there is no transition film layer) or is provided with a transition film layer. Further, the transition film layer may be a single-layer structure or a multi-layer structure (that is, one or more structural layers may be formed between the Cr-Zr-N alloy coating provided by the present invention and the substrate);

[0204] The Cr-Zr-N alloy coating is located on the surface of the coated product or a surface film layer is provided on the side of the Cr-Zr-N alloy coating away from the substrate. Furthermore, the surface film layer can be a single-layer structure or a multi-layer structure (that is, one or more structural layers can continue to be formed on the Cr-Zr-N alloy coating provided by the present invention).

[0205] In this application, unless otherwise specified, "transition layer" and "transition film layer" have the same meaning and can be used interchangeably. Both refer to a structural layer with transitional properties located between the substrate and the Cr-Zr-N alloy coating described in this application in a coated product, which can be a single-layer structure or a multi-layer structure.

[0206] In this application, unless otherwise specified, "surface layer" and "surface film layer" have the same meaning and can be used interchangeably. They both refer to the structural layer of the Cr-Zr-N alloy coating described in this application in the coated product, which is away from the substrate side and located on the surface of the product. It can be a single-layer structure or a multi-layer structure.

[0207] In some implementations, the Cr—Zr—N alloy coating 300 of the present application is in direct contact with the substrate 100 (in this case, there is no transition film layer).

[0208] In some implementations, a transition film layer 200 is provided between the Cr—Zr—N alloy coating 300 and the substrate 100 of the present application.

[0209] In some implementations, the Cr—Zr—N alloy coating 300 of the present application is located on the surface of the coated product.

[0210] In some implementations, a surface film layer 400 is further provided on a side of the Cr—Zr—N alloy coating 300 of the present application away from the substrate 100 .

[0211] In some implementations, the Cr—Zr—N alloy coating 300 of the present application is in direct contact with the substrate 100 (in this case, there is no transition film layer).

[0212] Figure 1 Schematic diagrams of the structures of the coated products in several embodiments of the present invention: (A) includes a substrate 100 and a Cr-Zr-N alloy coating 300 of the present application; (B) includes a substrate 100, a transition film layer 200 and a Cr-Zr-N alloy coating 300 of the present application; (C) includes a substrate 100, a transition film layer 200, a Cr-Zr-N alloy coating 300 of the present application and a surface film layer 400; (D) includes a substrate 100, a Cr-Zr-N alloy coating 300 of the present application and a surface film layer 400.

[0213] In the coated product, the position of the Cr-Zr-N alloy coating provided by the present invention can be flexibly set. It can directly contact the substrate or not directly contact the substrate. It can be used as a surface film layer or as an intermediate film layer located between the surface film layers of the substrate and other structures. When used as an intermediate film layer, other film layers are also provided on the outside of the Cr-Zr-N alloy coating, so that the Cr-Zr-N alloy coating of the present application does not need to be used as a surface film layer. The Cr-Zr-N alloy coating of the present invention in different positions can provide a high-gloss surface, excellent corrosion resistance, and high hardness characteristics. When the Cr-Zr-N alloy coating of the present application is used on the surface of a coated product, it can provide a high-brightness surface, so that the coating has both beautiful decorative and protective effects.

[0214] When the Cr—Zr—N alloy coating of the present invention is located on the surface of a plated product, the highly dense structure and surface smoothness of the Cr—Zr—N alloy coating can provide the plated product with a surface having high glossiness.

[0215] When the Cr-Zr-N alloy coating of the present invention is located on the surface of a coated product, the highly dense structure of the Cr-Zr-N alloy coating can also be used to obtain better coating reflection properties, thereby providing the coated product with a surface with high brightness.

[0216] In some embodiments, the application of the first aspect can be implemented by the following method: using a vapor deposition technique to deposit the constituent elements of the Cr-Zr-N alloy coating of the present application on at least a portion of the surface of the substrate according to a preset atomic ratio to form the Cr-Zr-N alloy coating of the present invention. It can be understood that the constituent elements of the Cr-Zr-N alloy coating include at least Cr, Zr and N.

[0217] The method of using the Cr-Zr-N alloy coating of the present application to provide a high gloss surface can adopt green and environmentally friendly manufacturing technology. The method is simple and easy to operate. It also has the advantages of being quantifiable, efficient, and repeatable, and is suitable for industrial applications.

[0218] In some embodiments, the vapor deposition technique is a physical vapor deposition technique. Further, the physical vapor deposition technique can be implemented by one or more of the following methods: vacuum evaporation, sputtering, arc plasma plating, ion plating, and molecular beam epitaxy.

[0219] In one embodiment, the physical vapor deposition method is magnetron sputtering coating.

[0220] In some embodiments, sputtering coating (such as magnetron sputtering coating) technology is used to deposit the constituent elements of the Cr—Zr—N alloy coating of the present invention on at least a portion of the surface of the substrate according to a preset atomic ratio.

[0221] In some embodiments, see Figure 2 The device shown. Figure 2 The device shown includes a vacuum chamber 1, a sample stage 2, a DC anode 3, a chromium target 4 and a zirconium target 5; wherein the chromium target 4 is a chromium target with radio frequency assisted DC cathode power supply, and the zirconium target 5 is a zirconium target with radio frequency assisted DC cathode power supply. The figure is not drawn in a 1:1 ratio, and the relative sizes of the components are drawn in the figure only as examples to facilitate the understanding of the present invention, but are not necessarily drawn in true proportions, and the proportions in the figure do not constitute a limitation of the present invention. The Cr-Zr-N alloy coating of the present invention can be formed by reactive sputtering with a N2-containing gas (such as an Ar / N2 mixed gas) in the vacuum chamber 1.

[0222] In some embodiments, the implementation method of the first aspect of the present invention, taking the sputtering coating method (such as magnetron sputtering coating) as an example, includes the following steps: under the condition of introducing a mixed gas containing argon and a nitrogen-containing gas, using one or more targets including chromium and zirconium, sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating of the present application on at least a portion of the surface of the substrate to form the Cr-Zr-N alloy coating of the present application. The nitrogen-containing gas can be but is not limited to nitrogen. At this time, the gas volume ratio of argon and nitrogen in the mixed gas can be (2-6):1, for example, 2:1, 3:1, 4:1, 5:1, 6:1, etc. When nitrogen is selected as the nitrogen-containing gas and the nitrogen content is controlled to a certain level, the performance of the Cr-Zr-N alloy coating of the present application can be further adjusted.

[0223] The target material may include one or more of a chromium target, a zirconium target and an alloy target. The alloy target includes at least two metal elements in the Cr-Zr-N alloy coating of the present application. In some preferred examples, the atomic ratio of the metal elements in the alloy target is the same as or close to the atomic ratio of the corresponding metal elements in the Cr-Zr-N alloy coating of the present application. In some embodiments, the alloy target is a chromium-zirconium-based alloy target, wherein the chromium-zirconium-based alloy target includes at least chromium and zirconium, such as a CrZr alloy target, a CrZrN alloy target, and the like. In some embodiments, the atomic ratio of Cr and Zr in the chromium-zirconium-based alloy target is 65%:35%. In some embodiments, the alloy target includes all metal elements in the Cr-Zr-N alloy coating of the present application. Examples of alloy targets can be found in Example 10 below.

[0224] In the present invention, unless otherwise specified, a "chromium-zirconium-based alloy target" includes at least chromium and zirconium, and may include or exclude other elements. When other elements are included, it is understood that the chemical composition of the target material should generally be within the preset chemical formula (Cr x Zr y N z )M aFor example, the chromium-zirconium-based alloy target may be a chromium-zirconium-nitrogen alloy target (ie, a CrZrN alloy target) composed of three elements: chromium, zirconium, and nitrogen.

[0225] In some embodiments, a chromium-zirconium alloy target consisting essentially of Cr and Zr is employed.

[0226] In some embodiments, a chromium-zirconium alloy target is used and mounted on Figure 2 The location of Zhongyuan chromium target 4, replace Figure 2 Zhongyuan chromium target 4.

[0227] In some embodiments, the implementation method of the first aspect of the present invention, taking the sputtering coating method (such as magnetron sputtering coating) as an example, includes the following steps: under the condition of introducing a mixed gas containing argon and nitrogen-containing gas, using a chromium target and a zirconium target or a chromium-zirconium alloy target (i.e., a CrZr alloy target), sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating of the present application on at least a portion of the surface of the substrate to form the Cr-Zr-N alloy coating of the present application.

[0228] In some embodiments, before the step of "sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating of the present application on at least a portion of the surface of the substrate", the following step is also included: cleaning the substrate. The method for cleaning the substrate can adopt a conventional cleaning method in the technical field (including but not limited to the field of decorative plating).

[0229] In some embodiments, the cleaning treatment of the substrate includes the following steps: placing the substrate in water for ultrasonic cleaning for 10-15 minutes, vacuum drying the cleaned substrate for 15-20 minutes, and placing the substrate on a sample stage of a sputtering coating (such as magnetron sputtering coating) device after drying. The sample stage may be a rotatable sample stage.

[0230] In one embodiment, the cleaning process of the substrate includes the following steps: placing the substrate in deionized water (DI water) for ultrasonic cleaning for 10-15 minutes, placing the cleaned substrate in a vacuum baking oven for baking for 15-20 minutes, and placing the substrate on a rotatable sample table in a vacuum chamber after drying.

[0231] In some embodiments, after the step of "cleaning the substrate", before the step of "sputtering and depositing the constituent elements of the Cr-Zr-N alloy coating of the present application on at least a portion of the surface of the substrate", the following step is also included: forming a transition film layer (the transition film layer can serve as a buffer film) on at least a portion of the surface of the cleaned substrate. For example, the constituent elements of the transition film layer can be deposited on at least a portion of the surface of the cleaned substrate.

[0232] In some embodiments, after the alloy coating of the present invention is formed on one side of the substrate, further deposition may be performed to form a surface film layer, and the surface film layer may be a single-layer structure or a multi-layer structure.

[0233] In some embodiments, the temperature of sputtering deposition is 30°C to 330°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 150°C, 200°C, 250°C, 300°C, 330°C, etc.

[0234] In some embodiments, the total gas pressure of the mixed gas including argon gas and nitrogen-containing gas is 0.4Pa to 1.0Pa, further such as 0.5Pa to 0.9Pa, and further such as 0.4Pa, 0.5Pa, 0.8Pa, 1.0Pa, etc.

[0235] In some embodiments, sputtering is performed by radio frequency assisted direct current sputtering, which can further improve the performance of the alloy coating formed by sputtering deposition compared to other preparation methods.

[0236] In some embodiments, the target material includes a chromium target, and the power density of the chromium target is 1.3 W / cm 2 ~6.7W / cm 2 , optional 1.3W / cm 2 ~6.0W / cm 2 .

[0237] In some embodiments, the target material includes a zirconium target, and the power density of the zirconium target is 1.0 W / cm 2 ~9.0W / cm 2 , optional 1.5W / cm 2 ~8.1W / cm 2 .

[0238] The target material may include a combination of a chromium target and a zirconium target.

[0239] In some embodiments, the target material includes an alloy target, and the alloy target includes at least two metal elements in the Cr-Zr-N alloy coating of the present application; optionally, the target material includes a chromium-zirconium-based alloy target, and the power density of the chromium-zirconium-based alloy target is 4W / cm 2 ~6W / cm 2 .

[0240] In some embodiments, the target material includes the chromium-zirconium alloy target, and the power density of the chromium-zirconium alloy target is 5 W / cm 2 .

[0241] In some embodiments, the target material is a chromium-zirconium alloy target with a power density of 4 W / cm 2 ~6W / cm2 , 5W / cm2 is optional 2 .

[0242] In some embodiments, the bias voltage of the substrate is -150 V to -20 V, such as -150 V, -120 V, -100 V, -90 V, -80 V, -60 V, -50 V, -40 V, -30 V, -20 V, etc.

[0243] In some embodiments, the nitrogen-containing gas has a gas flow rate of 5 sccm to 40 sccm, such as 5 sccm to 30 sccm, and such as 5 sccm, 10 sccm, 20 sccm, 25 sccm, 30 sccm, 40 sccm, etc. Further, the nitrogen-containing gas may be nitrogen gas.

[0244] In some embodiments, the sputtering deposition time is 10 min to 150 min, for example, 10 min, 15 min, 30 min, 45 min, 60 min, 90 min, 100 min, 120 min, etc. The thickness of the alloy coating of the present invention can be controlled by adjusting the deposition time. As the deposition time increases, the thickness of the alloy coating of the present invention increases.

[0245] In some embodiments, the deposition time is 120 min, and the thickness of the alloy coating is 1.0 μm.

[0246] In some embodiments, the nitrogen-containing gas is nitrogen, and the gas ratio of argon to nitrogen in the mixed gas is (2-6):1, such as 2:1, 3:1, 4:1, 5:1, 6:1, etc. When nitrogen is selected as the nitrogen-containing gas and the nitrogen content is controlled to a certain level, the performance of the alloy coating of the present invention can be further adjusted.

[0247] In some embodiments, the background vacuum of the vacuum chamber used is ≤5.0×10 -4 Pa. This pressure setting can ensure the collision between the sputtered particles and the gas molecules, and can also reduce the entry of impurities into the gas molecules during the deposition process, so as to improve the corrosion resistance, purity and bonding strength of the Cr-Zr-N alloy coating of the present invention.

[0248] It is understandable that argon gas and nitrogen-containing gas can be introduced into the vacuum chamber through a single path or mixed through a mixing cylinder and then enter the chamber, thereby reducing the impurity content of the alloy coating of the present invention and improving its performance.

[0249] In some embodiments, “using sputtering coating (such as magnetron sputtering coating) technology to load the constituent elements of the Cr-Zr-N alloy coating of the present application on at least a portion of the surface of the substrate according to a preset atomic ratio” includes the following steps: introducing a mixed gas containing argon and nitrogen-containing gas into the vacuum chamber 1, maintaining the pressure in the vacuum chamber 1 at 0.3Pa-1.2Pa, turning on the bias voltage and setting it to -150V to -20V, setting the power density of the Cr target 4 to 1.3W / cm 2 -6.7W / cm 2 , the power density of Zr target 5 was set to 0.5 W / cm 2 -7.9W / cm 2 , a Cr-Zr-N alloy coating is deposited on at least a portion of the surface of the substrate after cleaning; further, the Cr-Zr-N alloy coating with different film thicknesses can be obtained by controlling the film forming time.

[0250] In a second aspect of the present invention, a Cr-Zr-N alloy material is provided for use in providing a high gloss surface, wherein the Cr-Zr-N alloy material is as defined in the first aspect of the present invention, and the following embodiments may also be referred to. The Cr-Zr-N alloy material has a suitable atomic size mismatch and a special atomic ratio, and can form a Cr-Zr-N alloy coating used in the present invention with a high random mixing degree of "highly disordered and fully densely packed".

[0251] In some embodiments, the Cr-Zr-N alloy material satisfies the following two characteristics:

[0252] The X-ray diffraction pattern of the Cr-Zr-N alloy material has a peak within the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak within the range of 30° to 50° satisfies ≥ 2°;

[0253] In the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy material, the characteristic atomic spacing is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of The half-height width of at least one diffraction peak in the range satisfies ≥

[0254] Furthermore, the XRD test results of the Cr-Zr-N alloy material and the radial intensity profile results corresponding to the selected area electron diffraction pattern can also refer to the description of the radial intensity profile corresponding to the X-ray diffraction pattern and the selected area electron diffraction pattern in the Cr-Zr-N alloy coating in this article, and the corresponding optional and preferred methods can also be applied to the Cr-Zr-N alloy material.

[0255] Some specific embodiments are provided below.

[0256] The embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are preferably referred to the guidance provided in the present invention, and can also be based on the experimental manual or normal conditions in this area, and can also be based on the conditions recommended by the manufacturer, or refer to experimental methods known in the art.

[0257] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed.

[0258] The substrate in the following examples adopts a structure with a uniform material, for example, an aluminum alloy sheet, a stainless steel sheet, and a silicon sheet, which can be respectively referred to as an aluminum alloy substrate, a stainless steel substrate, and a silicon sheet substrate.

[0259] Test analysis method:

[0260] 1. Gloss test

[0261] The substrates used for the samples to be tested include stainless steel sheets, aluminum alloy sheets, and single crystal silicon polished square wafers with a crystal orientation of <1,0,0>.

[0262] Instrument: The glossiness of each film was tested using a gloss meter model ZGM1120 produced by Zehntner, Switzerland.

[0263] Test parameters: gloss range is 0-2000GU, measurement accuracy is ±1%, angle measurement is 20°, and each sample is tested on a flat surface at room temperature and the average value is taken after testing 5 matrix points.

[0264] The silicon wafer used as the substrate is a single crystal silicon polished square wafer with a crystal orientation of <1,0,0>, and its glossiness is 810.6GU. The aluminum alloy and stainless steel used as the substrate are polished wafers with a glossiness greater than 700GU.

[0265] 2. Salt spray corrosion resistance test of alloy coating

[0266] When the salt spray corrosion resistance test of the alloy coating is carried out, the sample to be tested is a substrate suitable for practical application, and the improvement degree of the corrosion resistance of the substrate by the alloy coating is detected. The surface material of the "substrate suitable for practical application" may include but is not limited to: aluminum alloy, stainless steel.

[0267] The ASTM B117 salt spray test standard is adopted, the pH value of the solution is 6.5-7.2, and the chemical composition of the solution is: sodium chloride (NaCl), deionized water and sodium hydroxide (NaOH).

[0268] 12 hours can be used as a sub-cycle of the salt spray corrosion resistance test.

[0269] The test cycle of alloy coatings prepared on substrates of different materials can be different, for example:

[0270] The test cycle for samples containing aluminum alloy substrates is 48h or 24h;

[0271] The test cycle of stainless steel substrate samples is 144h or 96h;

[0272] The test cycle of the copper sheet substrate sample is 12h.

[0273] The standard for "passing (OK)" salt spray corrosion resistance test is: after the sample is tested, there is no corrosion, no discoloration, and no rust on the appearance.

[0274] The standard for "failure (NG)" in the salt spray corrosion test is: after the sample is tested, corrosion, discoloration or rust is found on the surface.

[0275] 3. Hardness test of alloy coating

[0276] When testing the hardness of alloy coatings, the sample to be tested is a substrate suitable for actual application.

[0277] The surface material of the "substrate suitable for practical application" may include, but is not limited to: aluminum alloy, stainless steel, copper sheet.

[0278] When testing the hardness of the alloy coating, aluminum alloy and stainless steel are used as substrates, and the alloy coating is deposited on the aluminum alloy and stainless steel using preset preparation parameters to obtain the test sample for testing the hardness of the alloy coating. This is mainly due to the following considerations: During the nanoindentation test, when the probe penetrates the test sample, a strong pressure is formed. At this time, the substrate is required to have a certain toughness. If a brittle silicon wafer is used, cracking may occur during the test, resulting in inaccurate test results. Alloy materials are more suitable as the substrate to be tested for nanoindentation testing due to their excellent toughness. At the same time, the use of alloy materials as substrates to measure nanohardness is more universal in the field of nanohardness parameter characterization in the field of coated areas.

[0279] The hardness of each film or coating was tested using a nanoindenter model NHT3 produced by Anton-Paar, Austria. It was equipped with a tetrahedral Berkvich indenter, and the indentation depth was set to 100 nm. The load changed with the indentation depth. Five matrix points were tested for each sample and the average value was taken.

[0280] 4. Chroma value test of alloy coating

[0281] When testing the chromaticity value of the alloy coating, the sample to be tested uses a substrate that is suitable for practical application, and detects the degree of improvement of the density and other properties of the substrate by the alloy coating. The surface material of the "substrate that is suitable for practical application" may include but is not limited to: aluminum alloy, stainless steel, silicon wafer.

[0282] The L value, a value and b value of the samples were tested using a CM-3700A-U desktop spectrophotometer produced by Konica Japan. The F2 light source was selected as the light receiving system. Six matrix points were tested for each sample and the average value was taken.

[0283] Among them, the L value represents the brightness value, the a value represents the red and green chromaticity values, and the b value represents the yellow and blue chromaticity values.

[0284] The larger the L value, the higher the brightness, indicating that the coating surface is denser. The mechanism is as follows: the spectrophotometer reflects the incident light on the surface of the sample to be tested, and a reflectance curve is obtained. The amplitude of the curve can reflect the density of the material, which can be specifically characterized by the L value. For the same material, the higher its density, the larger the L value it displays.

[0285] 5. Morphology and composition test analysis of alloy coating

[0286] The samples to be tested all use silicon wafers as substrates.

[0287] Scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) testing methods

[0288] Morphology analysis: A scanning electron microscope (Regulus 8230, manufactured by Hitachi) was used.

[0289] Composition analysis: An energy dispersive X-ray spectrometer (EDX) attached to a Regulus 8230 scanning electron microscope produced by Hitachi was used, and the relative intensities of all elements were corrected by the ZAF method.

[0290] Test parameters: the electron acceleration voltage is 15 kilovolts, the beam current is 10 microamperes, the sample magnification is 200 times, and each sample is tested at 10 points and the average is taken.

[0291] 6. X-ray diffraction (XRD) test of alloy coating

[0292] When conducting XRD testing of alloy coatings, silicon wafers were used as substrates.

[0293] 6.1. Calculation of the half-height width of the diffraction peak in the XRD pattern

[0294] A German Bruker D8 Advance XRD diffractometer was used in the θ-2θ mode with Cu target Kα rays, a wavelength λ of 0.15406 nm, the X-ray tube controlled at 40 kV and 40 mA, a scanning range of 20° to 80°, and precise scanning measurements with a step size of 0.01°.

[0295] The steps for obtaining the half-width value are as follows: first, the diffraction peak is corrected, including: smoothing, background subtraction, removal of Kα2 line, subtraction of instrument broadening, etc., and the half-width value of the diffraction peak is obtained after fitting the diffraction peak with the Pseudo-Voigt function.

[0296] The EDP2XRD software (version 1.0.0, copyright by Hongwei Liu, The Australian Center for Microscopy and Microanalysis, The University of Sydney) was used to process the spectrum data: first, the scale was calibrated, then the center of the diffraction ring transmission spot was determined, and then converted into an XRD spectrum (where the electron wavelength is 0.00251 nanometers and the X-ray wavelength is 0.154 nanometers; the diffraction peak was deducted from the straight line background, and then fitted with the Voigt function to obtain the half-height width of the corresponding diffraction peak.

[0297] 6.2. Determine whether the XRD pattern of the alloy coating forms a broad peak

[0298] Method for judging whether there are broad peaks (sharp peaks) in the diffraction angle range of 2θ (°) from 30° to 50° in the XRD diffraction pattern: in the XRD spectrum, if the half-height width of the 2θ (°) diffraction peak is ≥2°, it is judged as a broad peak; if the half-height width of the 2θ (°) diffraction peak is <2°, it is judged as a sharp peak.

[0299] For a given 2θ(°) position, it can be any of the three states: no peak, sharp peak or broad peak.

[0300] 7. TEM test

[0301] When conducting TEM tests on alloy coatings, silicon wafers were used as substrates.

[0302] In the following embodiments, a selected area electron diffraction pattern is obtained by TEM technology, and then converted into a radial intensity profile, which is therefore also referred to as a radial intensity profile of a TEM selected area electron diffraction pattern.

[0303] 7.1. The half-width at half maximum of the diffraction ring of the TEM diffraction pattern is obtained by the following method:

[0304] TEM test sample preparation: The Helios 5CX model focused ion beam (FIB) of Thermo Fisher Co., Ltd. of the United States was used to thin the sample to obtain an electron transparent, TEM-observable planar sample.

[0305] SAED image acquisition: A Talos F200x transmission electron microscope (TEM) produced by Thermo Fisher Scientific Inc., USA, with an electron acceleration voltage of 200 kV and a selected area aperture diameter of 900 nm, was used to obtain the selected area electron diffraction pattern (SAED) of the sample.

[0306] Acquisition of radial intensity profile: The SAED spectrum data obtained above were processed using EDP2XRD software (version 1.0.0, copyright by Hongwei Liu, The Australian Center for Microscopy and Microanalysis, The University of Sydney): first, the scale was calibrated, then the center of the diffraction ring transmission spot was determined, and finally, it was converted into a radial intensity profile (where the electron wavelength is 0.00251 nanometers and the X-ray wavelength is 0.154 nanometers), with the characteristic atomic spacing as the horizontal axis and the diffraction intensity as the vertical axis.

[0307] The steps for obtaining the half-width value are as follows: subtract a straight line from the diffraction peak, and then fit it with the Voigt function to obtain the half-width value of the corresponding diffraction peak.

[0308] 7.2. Determine the radial intensity profile of the TEM selected area electron diffraction pattern Method to determine whether there is a broad peak within the range: the half-height width of the diffraction peak corresponding to the characteristic atomic spacing ≥ It is judged as a broad peak; the half-height width of the diffraction peak corresponding to the characteristic atomic spacing is < For a specific characteristic interatomic distance, it can be any of the three states: no peak, sharp peak or broad peak.

[0309] In the following examples, DI water means deionized water.

[0310] The stainless steel sheets, aluminum alloy sheets and silicon sheets in the following embodiments and comparative examples are of the same material. In the following examples, the stainless steel sheets in each example have the same specifications, the aluminum alloy sheets in each example have the same specifications, the silicon sheets in each example have the same specifications, and the copper sheets in each example have the same specifications. The surface properties of the substrates of the same material are basically the same.

[0311] In the following examples, the target material was sputtered by RF-assisted DC sputtering.

[0312] Non-limiting examples of using the Cr—Zr—N alloy coating of the present application for a high gloss surface can be found in, but are not limited to, Examples 1-13.

[0313] In the following examples, the reference to “there is only one broad peak” in the XRD diagram and the SAED-radial intensity profile diagram, unless otherwise specified, means there is only one characteristic peak, and the peak is a broad peak.

[0314] Example 1.

[0315] In this example, the chemical composition of the Cr-Zr-N alloy coating is Cr 81.6 Zr 13.7 N 4.7 .

[0316] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in deionized water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0317] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0318] Deposition of Cr-Zr-N alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 5 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 6:1, maintain the furnace pressure at 0.6 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 6 W / cm 2 , the power density of the Zr target was set to 1.5 W / cm 2 , depositing a Cr-Zr-N alloy coating, and controlling the film forming time so that the film thickness of the obtained Cr-Zr-N alloy coating is 1300nm;

[0319] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon wafers as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are also tested for salt spray corrosion resistance, hardness and color value; samples using silicon wafers as substrates are also tested for SEM and composition analysis, color value test, XRD analysis and TEM test.

[0320] According to the composition analysis, the composition of the Cr-Zr-N alloy coating on the substrate surface is Cr 81.6 Zr 13.7 N 4.7 .

[0321] The glossiness of the silicon wafer substrate sample tested was 939.2GU, the glossiness of the aluminum alloy substrate sample tested was 929.8GU, and the glossiness of the stainless steel substrate sample tested was 1030.3GU. In this example, the Cr-Zr-N alloy coating is a high-gloss coating.

[0322] The tested chromaticity value of silicon wafer substrate sample is L: 80.98, a: 0.24, b: 2.54, the tested chromaticity value of aluminum alloy substrate sample is L: 81.31, a: 0.26, b: 2.88, the tested chromaticity value of stainless steel substrate sample is L: 82.30, a: 0.20, b: 2.45, showing silvery white metallic color.

[0323] In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, showing excellent protection properties.

[0324] The hardness value of the aluminum alloy substrate sample tested is 13.7 GPa, and the hardness value of the stainless steel substrate sample tested is 14.6 GPa.

[0325] The SEM cross-section of the test sample was characterized. The cross-sectional morphology can be found in Figure 3 , XRD diffraction pattern, TEM-SAED pattern and radial intensity profile can be found at Figure 4 The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30°~50°, and the half-height width of the 2θ(°) diffraction angle in the XRD diffraction pattern in the range of 30°~50° is ≥2°, among which there is only one broad peak with a half-height width of 9.11° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0326] Example 2-13 adopts a method basically the same as Example 1, using a stainless steel sheet, an aluminum alloy sheet and a silicon sheet as substrates, respectively, and sputtering-depositing a Cr-Zr-N alloy coating on the surface of the substrate. The difference is that one or more preparation parameters are different in target power density, Ar and N2 gas volume ratio, N2 gas flow rate, furnace pressure and thickness of the Cr-Zr-N alloy coating, which can be seen in Table 1.

[0327] Some relevant parameters of Examples 1-13 and Comparative Examples 1-4 are also summarized in Table 1.

[0328]

[0329] Example 2

[0330] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating is Cr 15.0 Zr 80.3 N 4.7 .

[0331] In this embodiment, the target materials are Cr target and Zr target.

[0332] Stainless steel sheets, aluminum alloy sheets and silicon sheets are used as substrates respectively.

[0333] The steps of substrate pretreatment and plasma cleaning are the same as those in Example 1. The steps of depositing the Cr-Zr-N alloy coating are basically the same as those in Example 1. The differences are shown in Table 1.

[0334] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon wafers as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are also tested for salt spray corrosion resistance, hardness and color value; samples using silicon wafers as substrates are also tested for SEM and composition analysis, color value test, XRD analysis and TEM test.

[0335] According to the composition analysis, the composition of the Cr-Zr-N alloy coating on the substrate surface is Cr 15.0 Zr 80.3 N 4.7 .

[0336] The glossiness of the silicon wafer substrate sample tested was 1043.2GU, the glossiness of the aluminum alloy substrate sample tested was 891.5GU, and the glossiness of the stainless steel substrate sample tested was 1065.1GU, which are high-gloss coatings.

[0337] The tested chromaticity value of silicon wafer substrate sample is L: 77.40, a: 0.51, b: 6.24, the tested chromaticity value of aluminum alloy substrate sample is L: 74.30, a: 0.53, b: 6.58, the tested chromaticity value of stainless steel substrate sample is L: 75.55, a: 0.45, b: 6.32, showing silvery white metallic color.

[0338] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 22.3GPa, and the hardness value of the stainless steel substrate sample is 23.1GPa.

[0339] The SEM test results show that the Cr-Zr-N alloy coating has a dense structure.

[0340] The XRD test results show that the diffraction angle 2θ (°) in the XRD diffraction pattern has a broad peak in the range of 30° to 50°; the TEM test results show that the radial intensity profile of the TEM selected area electron diffraction pattern There is a broad peak in the range.

[0341] Example 3

[0342] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating is Cr 15.0 Zr 63.0 N 22.0 .

[0343] In this embodiment, the target materials are Cr target and Zr target.

[0344] Stainless steel sheets, aluminum alloy sheets and silicon sheets are used as substrates respectively.

[0345] The steps of substrate pretreatment and plasma cleaning are the same as those in Example 1. The steps of depositing the Cr-Zr-N alloy coating are basically the same as those in Example 1. The differences are shown in Table 1.

[0346] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon sheets as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are also tested for salt spray corrosion resistance and hardness; samples using silicon wafers as substrates are also tested for SEM and composition analysis, color value testing, XRD analysis and TEM testing.

[0347] According to the composition analysis, the composition of the Cr-Zr-N alloy coating on the substrate surface is Cr 15.0 Zr 63.0 N 22.0 .

[0348] The glossiness of the silicon wafer substrate sample tested was 1135.6GU, the glossiness of the aluminum alloy substrate sample tested was 1050.5GU, and the glossiness of the stainless steel substrate sample tested was 1120.6GU. In this example, the Cr-Zr-N alloy coating is a high-gloss coating.

[0349] The chromaticity value of the silicon wafer substrate sample tested is L: 78.12, a: 0.48, b: 5.78, and it is a silvery white metallic color.

[0350] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 16.8GPa, and the hardness value of the stainless steel substrate sample is 17.3GPa.

[0351] The test samples were subjected to SEM cross-section tests, and the SEM test results showed that the Cr-Zr-N alloy coating had a dense structure.

[0352] The XRD test results show that the diffraction angle 2θ (°) in the XRD diffraction pattern has a broad peak in the range of 30° to 50°; the TEM test results show that the radial intensity profile of the TEM selected area electron diffraction pattern There is a broad peak in the range.

[0353] Example 4

[0354] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating is Cr 64.3 Zr 13.7 N 22.0 .

[0355] In this embodiment, the target materials are Cr target and Zr target.

[0356] Stainless steel sheets, aluminum alloy sheets and silicon sheets are used as substrates respectively.

[0357] The steps of substrate pretreatment and plasma cleaning are the same as those in Example 1. The steps of depositing the Cr-Zr-N alloy coating are basically the same as those in Example 1. The differences are shown in Table 1.

[0358] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon wafers as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are tested for salt spray corrosion resistance and hardness; samples using silicon wafers as substrates are also tested for SEM and composition analysis, color value testing, XRD analysis and TEM testing.

[0359] According to the composition analysis, the composition of the Cr-Zr-N alloy coating on the substrate surface is Cr 64.3 Zr 13.7 N 22.0 .

[0360] The glossiness of the silicon wafer substrate sample tested was 1168.5GU, the glossiness of the aluminum alloy substrate sample tested was 1120.5GU, and the glossiness of the stainless steel substrate sample tested was 1180.6GU. In this example, the Cr-Zr-N alloy coating is a high-gloss coating.

[0361] The chromaticity value of the silicon wafer substrate sample tested is L: 78.94, a: 0.41, b: 5.32, and it is a silvery white metallic color.

[0362] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 17.2GPa, and the hardness value of the stainless steel substrate sample is 19.3GPa.

[0363] The test samples were subjected to SEM cross-section tests, and the SEM test results showed that the Cr-Zr-N alloy coating had a dense structure.

[0364] The XRD test results show that the diffraction angle 2θ (°) in the XRD diffraction pattern has a broad peak in the range of 30° to 50°; the TEM test results show that the radial intensity profile of the TEM selected area electron diffraction pattern There is a broad peak in the range.

[0365] Example 5

[0366] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating is Cr 75.3 Zr 14.3 N 10.4 .

[0367] In this embodiment, the target materials are Cr target and Zr target.

[0368] Stainless steel sheets, aluminum alloy sheets and silicon sheets are used as substrates respectively.

[0369] The steps of substrate pretreatment and plasma cleaning are the same as those in Example 1. The steps of depositing the Cr-Zr-N alloy coating are basically the same as those in Example 1. The differences are shown in Table 1.

[0370] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon wafers as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are tested for salt spray corrosion resistance and hardness; samples using silicon wafers as substrates are also tested for SEM and composition analysis, color value testing, XRD analysis and TEM testing.

[0371] According to the composition analysis, the composition of the Cr-Zr-N alloy coating on the substrate surface is Cr 75.3 Zr 14.3 N 10.4 .

[0372] The glossiness of the silicon wafer substrate sample tested was 1322.6GU, the glossiness of the aluminum alloy substrate sample tested was 1180.5GU, and the glossiness of the stainless steel substrate sample tested was 1230.6GU. In this example, the Cr-Zr-N alloy coating is a high-gloss coating.

[0373] The chromaticity value of the silicon wafer substrate sample tested is L: 81.36, a: 0.39, b: 4.98, and it is a silvery white metallic color.

[0374] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 17.1GPa, and the hardness value of the stainless steel substrate sample is 18.2GPa.

[0375] The test samples were subjected to SEM cross-section tests, and the SEM test results showed that the Cr-Zr-N alloy coating had a dense structure.

[0376] The XRD test results show that the diffraction angle 2θ (°) in the XRD diffraction pattern has a broad peak in the range of 30° to 50°; the TEM test results show that the radial intensity profile of the TEM selected area electron diffraction pattern There is a broad peak in the range.

[0377] Example 6

[0378] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating is Cr 29.7 Zr 50.1 N 20.2 .

[0379] In this embodiment, the target materials are Cr target and Zr target.

[0380] Stainless steel sheets, aluminum alloy sheets and silicon sheets are used as substrates respectively.

[0381] The steps of substrate pretreatment and plasma cleaning are the same as those in Example 1. The steps of depositing the Cr-Zr-N alloy coating are basically the same as those in Example 1. The differences are shown in Table 1.

[0382] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon sheets as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are also subjected to salt spray corrosion resistance tests, hardness tests and color value tests. Samples using silicon wafers as substrates are also subjected to SEM and composition analysis, color value tests, XRD analysis and TEM tests.

[0383] According to the composition analysis, the composition of the Cr-Zr-N alloy coating on the substrate surface is Cr 29.7 Zr 50.1 N 20.2 .

[0384] The glossiness of the silicon wafer substrate sample tested was 1101.5GU, the glossiness of the aluminum alloy substrate sample tested was 975.8GU, and the glossiness of the stainless steel substrate sample tested was 1170.5GU. In this example, the Cr-Zr-N alloy coating is a high-gloss coating.

[0385] The tested chromaticity value of silicon wafer substrate sample is L: 78.14, a: 0.51, b: 5.68; the tested chromaticity value of aluminum alloy substrate sample is L: 76.13, a: 0.52, b: 5.88; the tested chromaticity value of stainless steel substrate sample is L: 78.01, a: 0.42, b: 5.07, showing bright silver-white metallic color.

[0386] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 19.5GPa, and the hardness value of the stainless steel substrate sample is 21.7GPa.

[0387] The SEM cross-section of the test sample was characterized. The cross-sectional morphology can be found in Figure 5 , XRD diffraction pattern can be found at Figure 6 The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30°~50°, that is, the half-width of the diffraction angle 2θ(°) in the XRD diffraction pattern in the range of 30°~50° is ≥2°, and there is only one broad peak with a half-width of 5.66° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is a broad peak in the range.

[0388] Example 7

[0389] Using the same method as in Example 6, the chemical composition of the Cr-Zr-N alloy coating is Cr 29.7 Zr 50.1 N 20.2 , the only difference is that the thickness of the Cr-Zr-N alloy coating is adjusted to 50nm.

[0390] The glossiness of the silicon wafer substrate sample tested was 1223.3GU, the glossiness of the aluminum alloy substrate sample tested was 1060.5GU, and the glossiness of the stainless steel substrate sample tested was 1120.6GU. In this example, the Cr-Zr-N alloy coating is a high-gloss coating.

[0391] The tested chromaticity value of silicon wafer substrate sample is L: 79.22, a: 0.49, b: 5.21; the tested chromaticity value of aluminum alloy substrate sample is L: 77.23, a: 0.51, b: 5.98; the tested chromaticity value of stainless steel substrate sample is L: 78.81, a: 0.41, b: 5.27, showing silvery white metallic color.

[0392] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 9.1GPa, and the hardness value of the stainless steel substrate sample is 9.8GPa.

[0393] The test samples were subjected to SEM cross-section tests, and the SEM test results showed that the Cr-Zr-N alloy coating had a dense structure.

[0394] The XRD test results show that the diffraction angle 2θ (°) in the XRD diffraction pattern has a broad peak in the range of 30° to 50°; the TEM test results show that the radial intensity profile of the TEM selected area electron diffraction pattern There is a broad peak in the range.

[0395] Example 8

[0396] Using the same method as in Example 6, the chemical composition of the Cr-Zr-N alloy coating is Cr 29.7 Zr 50.1 N 20.2 The only difference is that the thickness of the Cr-Zr-N alloy coating is adjusted to 6μm.

[0397] The glossiness of the silicon wafer substrate sample tested was 910.2GU, the glossiness of the aluminum alloy substrate sample tested was 750.8GU, and the glossiness of the stainless steel substrate sample tested was 780.1GU. In this example, the Cr-Zr-N alloy coating is a high-gloss coating.

[0398] The tested chromaticity value of silicon wafer substrate sample is L: 77.64, a: 0.46, b: 5.33; the tested chromaticity value of aluminum alloy substrate sample is L: 75.23, a: 0.55, b: 6.08; the tested chromaticity value of stainless steel substrate sample is L: 76.81, a: 0.42, b: 5.57, showing silvery white metallic color.

[0399] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 23.8GPa, and the hardness value of the stainless steel substrate sample is 25.2GPa.

[0400] The test samples were subjected to SEM cross-section tests, and the SEM test results showed that the Cr-Zr-N alloy coating had a dense structure.

[0401] The XRD test results show that the diffraction angle 2θ (°) in the XRD diffraction pattern has a broad peak in the range of 30° to 50°; the TEM test results show that the radial intensity profile of the TEM selected area electron diffraction pattern There is a broad peak in the range.

[0402] Example 9. Containing doping elements

[0403] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating containing doping elements is Cr 29.7 Zr 50.1 N 15.2 C5, at this time, the atomic percentage of the doping element C in the Cr-Zr-N alloy coating is 5%.

[0404] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0405] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0406] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar, C2H2 and N2 gases, set the N2 gas flow rate to 30 sccm, the C2H2 gas flow rate to 6 sccm, set the gas volume to maintain the Ar: (C2H2 + N2) gas volume ratio at 2:1, maintain the furnace pressure at 0.6 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 2.6 W / cm 2 , the power density of the Zr target was set to 5 W / cm 2 , depositing Cr-Zr-NC alloy coating, and by controlling the film forming time, the obtained film thickness is 1000nm.

[0407] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon wafers as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are tested for salt spray corrosion resistance and hardness; samples using silicon wafers as substrates are also tested for SEM and composition analysis, color value testing, XRD analysis and TEM testing.

[0408] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 29.7 Zr 50.1 N 15.2 C5.

[0409] The glossiness of the silicon wafer substrate sample tested was 1060.1GU, the glossiness of the aluminum alloy substrate sample tested was 950.8GU, and the glossiness of the stainless steel substrate sample tested was 1150.5GU. In this example, the Cr-Zr-N alloy coating is a high-gloss coating.

[0410] The chromaticity value of the silicon wafer substrate sample tested is L: 77.96, a: 0.44, b: 5.63, and it is bright silver-white in color.

[0411] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 19.6GPa, and the hardness value of the stainless steel substrate sample is 22.1GPa.

[0412] The test samples were subjected to SEM cross-section tests, and the SEM test results showed that the Cr-Zr-N alloy coating had a dense structure.

[0413] The XRD test results show that the diffraction angle 2θ (°) in the XRD diffraction pattern has a broad peak in the range of 30° to 50°; the TEM test results show that the radial intensity profile of the TEM selected area electron diffraction pattern There is a broad peak in the range.

[0414] According to the experimental exploration results of the inventors, when other non-metallic doping elements (such as Si, B, O, etc.) or metal doping elements (such as Al) are used, when the atomic ratio of the doping elements is appropriate (such as 4at%, 2at%), it can also provide higher glossiness and excellent corrosion resistance. In some embodiments, in the salt spray corrosion resistance test experiment, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test. It can also have at least one broad peak in the diffraction angle 2θ (°) range of 30° to 50° in the XRD diffraction pattern, and the radial intensity profile of the TEM selected area electron diffraction pattern is There is at least 1 broad peak within the range.

[0415] "at%" means atomic percent, by number.

[0416] Example 10.

[0417] In this example, the chemical composition of the Cr-Zr-N alloy coating is Cr 61.4 Zr 33.2 N 5.4 , the preparation method is as follows:

[0418] In this embodiment, the target material is a chromium-zirconium alloy target. Figure 2The original Cr target at the position of the middle Cr target 4 was replaced with a CrZr alloy target having an atomic percentage of Cr and Zr of 65%:35%.

[0419] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, keep at room temperature (about 30°C) for 15 minutes.

[0420] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0421] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use a radio frequency assisted DC power supply to energize the CrZr alloy target, introduce Ar and N2 gas, set the N2 gas flow rate to 7 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 6:1, maintain the furnace pressure at 0.7 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the CrZr alloy target to 5 W / cm 2 , depositing a Cr-Zr-N alloy coating, and by controlling the film forming time, the resulting film thickness is made to be 2500nm.

[0422] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon wafers as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are tested for salt spray corrosion resistance, hardness and color value; samples using silicon wafers as substrates are also tested for SEM and composition analysis, color value test, XRD analysis and TEM test.

[0423] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 61.4 Zr 33.2 N 5.4 .

[0424] The glossiness of the silicon wafer substrate sample tested was greater than 900GU, the glossiness of the aluminum alloy substrate sample tested was 780.5GU, and the glossiness of the stainless steel substrate sample tested was 830.2GU. In this example, the Cr-Zr-N alloy coating is a high-gloss coating.

[0425] The L value of the chromaticity value of the silicon wafer substrate sample tested is >70, the chromaticity value of the aluminum alloy substrate sample tested is L: 79.05, a: 0.43, b: 3.54, and the chromaticity value of the stainless steel substrate sample tested is L: 81.74, a: 0.33, b: 3.04, which is silvery white in color.

[0426] In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, showing excellent protection properties.

[0427] The hardness value of the aluminum alloy substrate sample tested is 15.1 GPa, and the hardness value of the stainless steel substrate sample tested is 16.3 GPa.

[0428] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Figure 7 , XRD diffraction pattern, TEM-SAED pattern and radial intensity profile can be found at Figure 8 . The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed. The XRD test results show that the half-width of the 2θ(°) diffraction angle in the XRD diffraction pattern within the range of 30° to 50° all meets ≥2°, and there is only one broad peak with a half-width of 8.85° in the range of 30° to 50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0429] Example 11.

[0430] In this example, the chemical composition of the Cr-Zr-N alloy coating is Cr 60.9 Zr 26.1 N 13.0 , the preparation method is as follows:

[0431] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0432] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0433] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 14 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 3:1, maintain the furnace pressure at 0.7 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 5 W / cm 2 , the power density of the Zr target was set to 2.7 W / cm 2, depositing Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness is 1000nm.

[0434] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon wafers as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are tested for salt spray corrosion resistance, hardness and color value; samples using silicon wafers as substrates are also tested for SEM and composition analysis, color value test, XRD analysis and TEM test.

[0435] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 60.9 Zr 26.1 N 13.0 .

[0436] The glossiness of the silicon wafer substrate sample tested was greater than 900GU, the glossiness of the aluminum alloy substrate sample tested was 1010.2GU, and the glossiness of the stainless steel substrate sample tested was 1040.5GU. In this example, the Cr-Zr-N alloy coating is a high-gloss coating.

[0437] The L value of the chromaticity value of the silicon wafer substrate sample tested is >70, the chromaticity value of the aluminum alloy substrate sample tested is L: 79.21, a: 0.41, b: 3.91, and the chromaticity value of the stainless steel substrate sample tested is L: 79.95, a: 0.33, b: 3.73, showing a bright silver-white color.

[0438] In the salt spray corrosion resistance test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, showing excellent protection properties.

[0439] The hardness value of the aluminum alloy substrate sample tested is 11.8 GPa, and the hardness value of the stainless steel substrate sample tested is 13.7 GPa.

[0440] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Fig. 9 , XRD diffraction pattern, TEM-SAED pattern and radial intensity profile can be found at Fig.10 The SEM test results show that the Cr-Zr-N alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30°~50°, and the half-height width of all 2θ(°) peaks in the range of 30°~50° in the diffraction pattern is ≥2°, among which there is only one broad peak with a half-height width of 9.33° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0441] Example 12.

[0442] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating is Cr 53.8 Zr 40.0 N 6.2 , the preparation method is as follows:

[0443] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0444] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0445] Deposition of Cr-Zr-N alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 8 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 6:1, maintain the furnace pressure at 0.7 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 4.2 W / cm 2 , the power density of the Zr target was set to 3.5 W / cm 2 , depositing a Cr-Zr-N alloy coating, and by controlling the film forming time, the resulting film thickness is made to be 2500nm.

[0446] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon wafers as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are tested for salt spray corrosion resistance, hardness and color value; samples using silicon wafers as substrates are also tested for SEM and composition analysis, color value test, XRD analysis and TEM test.

[0447] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 53.8 Zr 40.0 N 6.2 .

[0448] The glossiness of the silicon wafer substrate sample tested was greater than 900GU, the glossiness of the aluminum alloy substrate sample tested was 920.4GU, and the glossiness of the stainless steel substrate sample tested was 970.6GU. In this example, the Cr-Zr-N alloy coating is a high-gloss coating.

[0449] The L value of the chromaticity value of the silicon wafer substrate sample tested is >70, the chromaticity value of the aluminum alloy substrate sample tested is L: 77.02, a: 0.52, b: 4.99, and the chromaticity value of the stainless steel substrate sample tested is L: 79.36, a: 0.40, b: 4.49, which is silvery white in color.

[0450] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 16.1GPa, and the hardness value of the stainless steel substrate sample is 18.3GPa.

[0451] The SEM cross-section of the test sample was characterized. The cross-sectional morphology can be found in Fig.11 , XRD diffraction pattern, TEM-SAED pattern and radial intensity profile can be found at Fig.12 The SEM test results show that the alloy coating has a dense structure and no through-column cracks are observed; the XRD test results show that the diffraction angle 2θ(°) in the XRD diffraction pattern has a broad peak in the range of 30°~50°, and the half-width of the 2θ(°) diffraction angle in the XRD diffraction pattern in the range of 30°~50° is ≥2°, among which there is only one broad peak with a half-width of 8.42° in the range of 30°~50°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0452] Example 13.

[0453] In this embodiment, the chemical composition of the Cr-Zr-N alloy coating is Cr 54.8 Zr 35.1 N 10.1 , the preparation method is as follows:

[0454] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0455] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0456] Deposition of Cr-Zr-N alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 12 sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 3:1, maintain the furnace pressure at 0.7 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 4.3 W / cm 2 , the power density of the Zr target was set to 3.1 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 2200nm.

[0457] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon wafers as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are tested for salt spray corrosion resistance, hardness and color value; samples using silicon wafers as substrates are also tested for SEM and composition analysis, color value test, XRD analysis and TEM test.

[0458] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 54.8 Zr 35.1 N 10.1 .

[0459] The glossiness of the silicon wafer substrate sample tested was greater than 900GU, the glossiness of the aluminum alloy substrate sample tested was 990.5GU, and the glossiness of the stainless steel substrate sample tested was 1020.2GU. In this example, the Cr-Zr-N alloy coating is a high-gloss coating.

[0460] The L value of the chromaticity value of the silicon wafer substrate sample tested is >70, the chromaticity value of the aluminum alloy substrate sample tested is L: 76.82, a: 0.54, b: 5.99, and the chromaticity value of the stainless steel substrate sample tested is L: 78.16, a: 0.45, b: 5.49, showing a bright silver-white color.

[0461] In the salt spray corrosion test, the aluminum alloy substrate sample can pass the 48h test, and the stainless steel substrate sample can pass the 144h test, which has excellent protection characteristics. The hardness value of the aluminum alloy substrate sample is 15.9GPa, and the hardness value of the stainless steel substrate sample is 17.8GPa.

[0462] SEM test results show that the alloy coating has a dense structure and no through-holes are observed. XRD diffraction patterns, TEM-SAED patterns and lattice spacing-intensity quantitative spectra can be found at Fig.13 The XRD diffraction pattern has only one broad peak in the range of 30° to 50° at the diffraction angle 2θ (°), and the half-height width is 9.25°; the radial intensity profile of the TEM selected area electron diffraction pattern is There is only one broad peak in the range, and the half-height width is

[0463] Comparative Example 1.

[0464] In this comparative example, the chemical composition of the alloy coating is Cr 57.5 Zr 5.0 N 37.5 , the preparation method is as follows:

[0465] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heated to 150°C, and kept at this temperature for 15 minutes. The silicon wafer used as the substrate is a single crystal silicon polished square wafer with a crystal orientation of <1,0,0>, and a glossiness of 810.6GU.

[0466] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0467] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 45 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 2:1, maintain the furnace pressure at 0.8 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 4.6 W / cm 2 , the power density of the Zr target was set to 0.5 W / cm 2 , depositing a Cr-Zr-N protective coating, and by controlling the film formation time, the obtained film thickness is 1400nm.

[0468] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon wafers as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are also tested for salt spray corrosion resistance, hardness and color value; samples using silicon wafers as substrates are tested for SEM and composition analysis and color value.

[0469] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 57.5 Zr 5.0 N 37.5 .

[0470] The glossiness of the silicon wafer substrate sample tested was 620.5GU, the glossiness of the aluminum alloy substrate sample tested was 488.9GU, and the glossiness of the stainless steel substrate sample tested was 538.6GU, all of which were relatively low.

[0471] The tested chromaticity value of silicon wafer substrate sample is L: 72.68, a: 0.59, b: 3.95; the tested chromaticity value of aluminum alloy substrate sample is L: 72.35, a: 0.61, b: 4.03; the tested chromaticity value of stainless steel substrate sample is L: 75.88, a: 0.53, b: 3.93, which is silvery white in color.

[0472] In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <24h), and the stainless steel substrate sample failed the 144h test (NG, protection time <48h), with poor corrosion resistance. The hardness value of the aluminum alloy substrate sample was 17.9GPa, and the hardness value of the stainless steel substrate sample was 18.8GPa.

[0473] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Fig.14 , the alloy coating film has crystal defects and the structure is not dense.

[0474] Comparative Example 2.

[0475] In this comparative example, the chemical composition of the alloy coating is Cr 83.0 Zr 13.5 N 3.5 , the preparation method is as follows:

[0476] Pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heated to 150°C, and kept at this temperature for 15 minutes. The silicon wafer used as the substrate is a single crystal silicon polished square wafer with a crystal orientation of <1,0,0>, and its glossiness is 810.6GU.

[0477] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0478] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 4 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 6:1, maintain the furnace pressure at 0.6 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 6.1 W / cm 2 , the power density of the Zr target was set to 1.4 W / cm 2 , deposited Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness was 1300nm.

[0479] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon sheets as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are tested for salt spray corrosion resistance and hardness; samples using silicon wafers as substrates are also tested for color value, SEM and composition analysis.

[0480] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 83.0 Zr 13.5 N 3.5 .

[0481] The glossiness of the silicon wafer substrate sample tested was 850.5GU, the glossiness of the aluminum alloy substrate sample tested was 650.5GU, and the glossiness of the stainless steel substrate sample tested was 675.5GU, which are relatively low.

[0482] The chromaticity value of the silicon wafer substrate sample tested was L: 75.94, a: 0.25, b: 2.45, and it was silvery white in color.

[0483] In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <24h), and the stainless steel substrate sample failed the 144h test (NG, protection time <48h), and did not have the protective properties for the alloy substrate. The hardness value of the aluminum alloy substrate sample was 13.4GPa, and the hardness value of the stainless steel substrate sample was 14.1GPa

[0484] SEM cross-section test of the test sample showed that the alloy coating film had crystal defects and the structure was not dense.

[0485] Comparative Example 3.

[0486] In this comparative example, the chemical composition of the alloy coating is Cr 37.8 Zr 16.2 N 46 , the preparation method is as follows:

[0487] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0488] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0489] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 52 sccm, set the gas volume to maintain the Ar: N2 gas volume ratio of 2:1, maintain the furnace pressure at 0.9 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 3.5 W / cm 2 , the power density of the Zr target was set to 1.8 W / cm 2 , depositing Cr-Zr-N alloy coating, and by controlling the film forming time, the obtained film thickness is 1000nm.

[0490] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon wafers as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are tested for salt spray corrosion resistance, hardness and color value; samples using silicon wafers as substrates are also tested for SEM and composition analysis, color value test, XRD analysis and TEM test.

[0491] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 37.8 Zr 16.2 N 46 .

[0492] The glossiness of the silicon wafer substrate sample tested was less than 900GU, the glossiness of the aluminum alloy substrate sample tested was 460.6GU, and the glossiness of the stainless steel substrate sample tested was 490.5GU, which are relatively low.

[0493] The L value of the chromaticity value of the silicon wafer substrate sample test is <70, the chromaticity value of the aluminum alloy substrate sample test is L: 61.87, a: 0.57, b: 4.45, and the chromaticity value of the stainless steel substrate sample test is L: 67.38, a: 0.49, b: 4.29. The color is dull and does not have a metallic color.

[0494] In the salt spray corrosion resistance test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <24h), and the stainless steel substrate sample failed the 144h test (NG, protection time <48h), and the protection properties were poor.

[0495] The hardness value of the aluminum alloy substrate sample tested is 16.6 GPa, and the hardness value of the stainless steel substrate sample tested is 18.1 GPa.

[0496] The SEM cross-section test was performed on the test sample. The cross-sectional morphology can be found in Fig.15 The test results of XRD diffraction pattern, TEM selected area electron diffraction pattern and radial intensity profile can be found at Fig.16 . The SEM test results show that the alloy coating film has a loose structure and obvious through-column cracks. The XRD test results show that the diffraction angle 2θ (°) in the XRD diffraction pattern has two peaks in the range of 30° to 50° and both are sharp peaks. Among them, the half-height widths of the two peaks in the range of 30° to 50° are 0.66° and 1.24° respectively. The radial intensity profile of the TEM selected area electron diffraction pattern is There are 2 peaks in the range, with half-height widths of That is, there are two peaks.

[0497] Comparative Example 4.

[0498] In this comparative example, the chemical composition of the alloy coating is Cr 39.6 Zr 19.4 N 41 , the preparation method is as follows:

[0499] Substrate pretreatment: Stainless steel sheets, aluminum alloy sheets and silicon wafers with an aspect ratio of 50 mm × 50 mm were ultrasonically cleaned in DI water for 15 minutes, dried in a baking oven and placed in the vacuum chamber of the coating machine. The vacuum chamber was evacuated to 5 × 10 -4 Pa, heat to 150℃ and keep constant temperature for 15 minutes.

[0500] Plasma cleaning: introduce Ar gas, maintain the furnace pressure at 2.0Pa, turn on the bias voltage and set it to -800V, and perform plasma cleaning for 20 minutes. The purpose is to use plasma etching to remove tiny impurities on the sample surface.

[0501] Deposition of alloy coating: Turn on the sample stage turret, set the speed to 6 revolutions per minute, adjust the distance from the sample stage to the target surface to 8 cm, use RF-assisted DC power supply to energize the Cr target and Zr target, introduce Ar and N2 gas, set the N2 gas flow rate to 45 sccm, set the gas volume to maintain the Ar: N2 gas ratio of 2:1, maintain the furnace pressure at 0.8 Pa, turn on the bias voltage, set it to -100 V, and set the power density of the Cr target to 4.6 W / cm 2, the power density of the Zr target was set to 2.2 W / cm 2 , depositing a Cr-Zr-N alloy coating. By controlling the film forming time, the thickness of the obtained alloy coating film is 1400nm.

[0502] The gloss test uses stainless steel sheets, aluminum alloy sheets and silicon wafers as substrates for depositing alloy coatings. Samples using stainless steel sheets and aluminum alloy sheets as substrates are tested for salt spray corrosion resistance, hardness and color value; samples using silicon wafers as substrates are also tested for SEM and composition analysis, color value test, XRD analysis and TEM test.

[0503] According to the composition analysis, the alloy coating on the substrate surface is composed of Cr 39.6 Zr 19.4 N 41 .

[0504] The glossiness of the silicon wafer substrate sample tested was less than 900GU, the glossiness of the aluminum alloy substrate sample tested was 440.8GU, and the glossiness of the stainless steel substrate sample tested was 470.2GU, which are relatively low.

[0505] The L value of the chromaticity value of the silicon wafer substrate sample tested is <70, the chromaticity value of the aluminum alloy substrate sample tested is L: 64.71, a: 0.58, b: 4.15, and the chromaticity value of the stainless steel substrate sample tested is L: 66.38, a: 0.49, b: 4.27, which is silvery white in color.

[0506] In the salt spray corrosion resistance test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate.

[0507] The hardness value of the aluminum alloy substrate sample tested is 15.4 GPa, and the hardness value of the stainless steel substrate sample tested is 17.2 GPa.

[0508] The SEM test results show that the alloy coating film has crystal defects, the structure is not dense, and there are obvious through-column gaps. The test results of XRD diffraction pattern, TEM selected area electron diffraction pattern and radial intensity profile can be found in Fig.17 The XRD test results show that the diffraction angle 2θ (°) in the XRD diffraction pattern has two peaks in the range of 30° to 50°, and both are sharp peaks. Among them, the half-height widths of the two peaks in the range of 30° to 50° are 1.87° and 1.02° respectively. The radial intensity profile of the TEM selected area electron diffraction pattern is There are 2 peaks in the range, with half-height widths of That is, there is one peak.

[0509] Comparative Example 5. Alloy coating thickness 50nm

[0510] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 50nm.

[0511] In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate. The hardness value of the aluminum alloy substrate sample was 9.1GPa, and the hardness value of the stainless steel substrate sample was 9.8GPa.

[0512] Comparative Example 6: Alloy coating thickness 1000nm

[0513] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 1000nm.

[0514] In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate. The hardness value of the aluminum alloy substrate sample was 16.5GPa, and the hardness value of the stainless steel substrate sample was 17.9GPa.

[0515] Comparative Example 7: Alloy coating thickness 2500nm

[0516] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 2500nm.

[0517] In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate. The hardness value of the aluminum alloy substrate sample was 20.5GPa, and the hardness value of the stainless steel substrate sample was 21.1GPa.

[0518] Comparative Example 8: Alloy coating thickness 6000nm

[0519] The same method as in Comparative Example 4 was used, and the chemical composition of the alloy coating was Cr 39.6 Zr 19.4 N 41 The difference is that the thickness of the alloy coating is different, changing from 1400nm to 6000nm.

[0520] In the salt spray corrosion test, the aluminum alloy substrate sample failed the 48h test (NG, protection time <12h), and the stainless steel substrate sample failed the 144h test (NG, protection time <24h), and did not have the protective properties for the substrate. The hardness value of the aluminum alloy substrate sample was 22.1GPa, and the hardness value of the stainless steel substrate sample was 23.7GPa.

[0521] Comparative Examples 9-11. No protective coating

[0522] Aluminum alloy bare chips, stainless steel bare chips and copper bare chips were respectively subjected to salt spray corrosion resistance tests. The results showed that obvious corrosion occurred within 12 hours.

[0523] Result analysis:

[0524] The coating surfaces of the Cr-Zr-N alloy coating of the present application in the above-mentioned embodiments (such as embodiments 1-13) all have high glossiness, excellent corrosion resistance, and high hardness.

[0525] The implementation method of using the Cr-Zr-N alloy coating of the present application to provide a high-gloss surface can adopt green and environmentally friendly manufacturing technology.

[0526] Based on a certain coating thickness, the Cr—Zr—N alloy coating of the present application in each embodiment (such as embodiments 1-13) has a relatively high hardness, and has both excellent corrosion resistance and high hardness characteristics.

[0527] According to the data of each embodiment, as the N content changes, the glossiness first increases and then gradually decreases, and the L value also changes synchronously and in the same manner; in embodiments 1-13, the glossiness value and the L value are both the largest in embodiment 5.

[0528] According to the results of XRD test and TEM selected area electron diffraction test, the Cr-Zr-N alloy coating of the present application (Examples 1-13) in each embodiment has at least one broad peak (furthermore, all are broad peaks, and the half-height width is ≥2°) in the diffraction angle 2θ (°) in the XRD diffraction pattern within the range of 30° to 50°, and the radial intensity profile of the TEM selected area electron diffraction pattern is 2θ (°). There is at least one broad peak in the range (further, all are broad peaks, and the half-height width is ≥ ); The Cr-Zr-N alloy coatings of the present application all have a "highly disordered and fully densely packed" atomic arrangement, which is consistent with the highly dense structure in the SEM morphology characterization results.

[0529] The bare substrate chips of Comparative Examples 9-11, without a protective coating, were not resistant to salt spray corrosion and suffered obvious corrosion within 12 hours.

[0530] The glossiness of the coating in Comparative Example 1-2 is low, and the corrosion resistance is poor, and the corrosion resistance test fails. The reason for the failure of the corrosion resistance test is speculated to be: the presence of penetrating column gaps in the film structure leads to gaps in the film, and the corrosive solution quickly passes through the gaps and contacts the substrate, resulting in the failure of the corrosion resistance of the coating. The reason for the low glossiness may be that the growth structure of the penetrating column gaps causes a large surface roughness.

[0531] The corrosion resistance of the coatings in Comparative Examples 3-4 is poor. The possible reasons are: the film structure is not dense and there are gaps, such as penetrating column gaps, which cause the corrosive solution to quickly pass through the gaps and contact the substrate, thereby causing the corrosion resistance of the coating to fail.

[0532] For the alloy coatings of different thicknesses in Comparative Examples 5-8, their hardness and corrosion resistance are significantly inferior to those of the Cr-Zr-N alloy coating of the present invention of the same thickness. Among them, even if Comparative Example 8 adopts a thickness of up to 6000nm (6 microns), its hardness is relatively high, but its corrosion resistance is still relatively poor. The reasons may be speculated to be: the film structure is not dense, and there are gaps, such as through-column gaps, which cause the corrosive solution to quickly pass through the gaps and contact the substrate, thereby causing the corrosion resistance of the coating to fail; although increasing the thickness of the coating can increase the hardness of the coating, the structural defects still exist. The Cr-Zr-N alloy coating of the present invention can have both excellent corrosion resistance and high hardness characteristics at a relatively low thickness, thereby saving raw materials, simplifying the process, shortening the production cycle, and significantly reducing costs. When the thickness of the alloy coating is relatively thin, the formed coated product can present a silvery-white metallic color, which is close to the metallic color of the substrate, and is more conducive to achieving a beautiful decorative effect without changing the color of the substrate.

[0533] According to the data of the embodiments and comparative examples, it can be known that the alloy coatings provided by the present invention have high gloss and excellent corrosion resistance. The aluminum alloy surface can pass the 48h salt spray test, and the stainless steel surface can pass the 144h salt spray test.

[0534] In addition, the inventors' exploratory experiments found that the alloy coating further deposited based on the Cr-Zr-N alloy coating of the present application is conducive to obtaining a smoother and denser surface. Using silicon wafers as substrates, the Cr-Zr-N alloy coatings of the present application of Examples 3 and 4, and the Cr-Zr-N alloy coatings of Comparative Examples 3 and 4 were deposited, respectively, with a coating thickness of 1000 nm, and then the Cr-Zr-N alloy coating of the present application of Example 5 was deposited, respectively. After the salt spray corrosion resistance test, both had excellent corrosion resistance and high gloss surface, but the gloss value of the surface alloy coating formed based on the alloy coatings of Comparative Examples 3 and 4 was slightly lower than the gloss value of the surface alloy coating formed based on the alloy coatings of Examples 3 and 4.

[0535] The technical features of the above-mentioned embodiments and examples can be combined in any appropriate manner. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments and examples are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0536] The above embodiments only express several implementation methods of the present invention, which is convenient for understanding the technical solution of the present invention in detail, but it cannot be understood as limiting the scope of protection of the present invention. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present invention, several variations and improvements can be made, which all belong to the protection scope of the present invention. In addition, it should be understood that after reading the above teaching content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and the equivalent forms obtained also fall within the protection scope of the present invention. It should also be understood that the technical solutions obtained by those skilled in the art on the basis of the technical solution provided by the present invention through logical analysis, reasoning or limited experiments are all within the protection scope of the claims attached to the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the content of the attached claims, and the description and drawings can be used to explain the content of the claims.

Claims

1. A Cr-Zr-N alloy coating is used to provide a high gloss surface, characterized in that: The Cr-Zr-N alloy coating is used to provide the surface of the coated product or to serve as a forming base surface for an adjacent alloy coating; The Cr-Zr-N alloy coating comprises a Cr-Zr-N alloy material, the chemical formula of which is (Cr x Zr y N z )M a , wherein M is a doping element, x, y, z and a are each independently an atomic ratio, and a is 0 or a positive number; taking the sum of x, y and z as 100, 15.0≤x≤81.6, 13.7≤y≤80.3, 4.7≤z≤22.0; The glossiness test conditions of the Cr-Zr-N alloy coating meet at least one of the following conditions: under the test condition of measuring at an angle of 20° and taking aluminum alloy as the forming base surface of the Cr-Zr-N alloy coating, the glossiness value of the high glossiness surface is ≥750GU; Under the test condition of measuring at an angle of 20° with stainless steel as the forming base surface of the Cr-Zr-N alloy coating, the gloss value of the high gloss surface is ≥780GU; and Under the test condition of measuring at an angle of 20° and taking a silicon wafer as the molding base surface of the Cr—Zr—N alloy coating, the gloss value of the high gloss surface is ≥900 GU.

2. The use according to claim 1, characterized in that Under the test condition of measuring at an angle of 20° and taking a silicon wafer as the molding base surface of the Cr—Zr—N alloy coating, the gloss value of the high-gloss surface is ≥1000 GU.

3. The use according to claim 2, characterized in that Under the test condition of measuring at an angle of 20° and taking a silicon wafer as the molding base surface of the Cr—Zr—N alloy coating, the gloss value of the high-gloss surface is ≥1100 GU.

4. The use according to claim 1, characterized in that Taking the sum of x, y and z as 100, 29.7≤x≤81.6, 13.7≤y≤50.1, 4.7≤z≤20.

2.

5. The use according to any one of claims 1 to 4, characterized in that: According to the Lab test method, the brightness value L of the high gloss surface is ≥70.

6. The use according to any one of claims 1 to 5, characterized in that: The Cr-Zr-N alloy coating also serves as a corrosion-resistant coating, a hard coating or a hard corrosion-resistant coating.

7. The use according to any one of claims 1 to 6, characterized in that: The Cr-Zr-N alloy coating meets the following two characteristics: The X-ray diffraction pattern of the Cr-Zr-N alloy coating has a peak in the diffraction angle 2θ (°) range of 30° to 50°, and the half-height width of at least one 2θ (°) diffraction peak in the range of 30° to 50° satisfies ≥ 2°; In the radial intensity profile corresponding to the selected area electron diffraction pattern of the Cr-Zr-N alloy coating, the characteristic atomic spacing is taken as the abscissa and the diffraction intensity is taken as the ordinate. There are diffraction peaks in the range of The half-width of at least one diffraction peak in the range satisfies 8. The use according to any one of claims 1 to 7, characterized in that: a=0 or 0, the doping element is a non-metallic element, a metallic element or a combination thereof; 9. The use according to any one of claims 1 to 8, characterized in that: The non-metallic elements include one or more of O, C, B, Si and Ar; The metal elements include one or more of Ti, V, Nb, Mo, Hf, Ta, W, Ni, Mo, Fe, Ag, Au, Cu and Al. The Cr-Zr-N alloy coating is formed on the surface of any of the following substrates: one of alloys, elemental metals and inorganic non-metallic materials.

10. The use according to any one of claims 1 to 9, characterized in that: The thickness of the Cr-Zr-N alloy coating is d min ~6μm, where d min Selected from 10nm to 50nm.

11. The use according to any one of claims 1 to 10, characterized in that: The Cr-Zr-N alloy coating is formed on the surface of any of the following substrates: one of aluminum alloy, silicon-based material and stainless steel.

12. The use according to claim 11, characterized in that The Cr—Zr—N alloy material is as defined in any one of claims 1 to 5 and 8 to 9.

13. Application of a Cr-Zr-N alloy material for providing a high gloss surface, characterized in that: ​

Citation Information

Cited By

  • Cr-ti-n alloy film, cr-ti-n alloy coating, alloy film product and use

    WO2025261349A1